Accelerated surface reconstruction via a controllable boronization strategy for efficient water oxidation - Wankun Li; Meijia Liu; Shuo Zheng; Yongjia Li; Yujia Liu; Lin Wu; Shuai Chen; Lixiang Li; Chengguo Sun; Han Zhang; Baigang An (Fuel, 2027)

Spatial scales effects on the geographical origin identification of PGI kiwifruit by stable isotope and mineral elemental fingerprinting - Jiali Li; Jianping Qian; Qian Chen; Zihan Liu; An Li; Xintao Lin; Boyu Shuai; Jiangmin Zhou; Junyi Wang; Zihan Bian; Linghuan Ouyang; Ming Li (Food Control, 2027)

Correction to: Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Sequence dynamics and plastome evolution: decoding the complete chloroplast genome of Oenothera drummondii and comparative analysis within Oenothera (Onagraceae) - Chang An; Wenbo Xu; Yixin Yao; Min Li; Yanxiang Lin; S. V. G. N. Priyadarshani; Aya Elderini; Yan Cheng; Site Luo; Yuan Qin; Ping Zheng (Functional & Integrative Genomics, 2026)

Unlocking the Size-Dependent mechanism of CO2 reduction on Carbon-Supported Nin clusters - Yimeng Sun; Lin Tao; Meixu Lu; Xin Quan; Mingjie Wu; Javed Rehman; Nan Wang; Lixiang Li; Baigang An (Fuel, 2026)

Chemical-free closed-loop conversion of nitrate into struvite fertilizer via exsolved high-entropy perovskite electrocatalyst - Li-Hui Yang; Yi-Heng Liu; Si-Hao Lv; Man-Ting Liao; Hui Lin; Wei Li; Cao Yang; An-Qi Wang; Hao-Yi Cheng (Journal of Environmental Chemical Engineering, 2026)

Triazine and other herbicides in sediments of lower Laurentian Great Lakes – pre- and post-depositional mobility and in-situ degradation - Shanshan Zhou; Huan He; Tian Lin; Jiehong Guo; Xiusen Yang; Xinyue Jia; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Environmental Pollution, 2026)

Corrigendum to “flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction” [Chem. Eng. J. 521 (2025) 166451] - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2026)

Microplastic-derived dissolved organic matter is associated with increased N2O emissions and altered denitrification-related microbial signatures in constructed wetlands - Yong Lin; Dianpeng Li; Mengshuo Liu; Teng Wen; Xuebin Lu; Jun Chen; Shuqing An (Journal of Hazardous Materials, 2026)

Root exudates recruit microbial allies to override their own mobilization effects for cadmium immobilization in intercropped rice - Ye Li; Jie Hou; Mengqi Liu; Hongan Chen; Xinyi Wang; Peizhe Sun; Lin Zhao; Yanpo Yao; Zhaolin Du; Yi An (Journal of Hazardous Materials, 2026)

PhenolFingerprint DB: an open-access platform for phenolic fingerprinting, quantification, and automated species authentication, validated on 93 floral and herbal plants - Tingwei Li; Xiaodong Liu; Xu Jin; Quanying Sun; Yulu Wang; Lin Yang; Yesong Zhang; Wenlong Wei; Hua Qu; Qirui Bi; Ping Li; Xiangmei Chen; et al. (Food Chemistry, 2026)

The effect of thermal ultrasonic treatment on the interaction between tea polyphenols and goat milk proteins at different ratios - Nanqi Zhao; Yutong Ma; Xiaosong Feng; Wenbang An; Xin Wang; Lin Chen; Qingkun Zeng; Ling Li; Xianchao Feng (Food Chemistry, 2026)

Constructing hydrophobic carbon-encapsulated Fe5C2 catalysts for enhanced Fischer-Tropsch synthesis to olefins with reduced CO2 selectivity - Ranqing Zhang; Xuan Zhou; Derun Li; Kun Gong; Yunlei An; Jing Xin; Peipei Zhang; Yanfang Song; Yuanyuan Dai; Tiejun Lin; Liangshu zhong (Chemical Engineering Journal, 2026)

Myeloid-derived suppressor cells-guided mesoporous silica nanoplatform delivering a BET inhibitor exerts anticancer effects by reprogramming the immunosuppressive tumor microenvironment - Li-Chan Chang; Li Xu; Yin-Fen Liu; Chang-An Lin; Si-Han Wu; Wen-Pin Su (Chemical Engineering Journal, 2026)

Surfactant Regulation of the Solution-Mediated Phase Transformation of Nitrofurantoin Anhydrate to Monohydrate - Zhuangzhuang Chen; Xiyan Wang; An Chen; Lin Li; Zhongting Zhuang; Minshan Guo; Ting Cai (Pharmaceutical Research, 2026)

Shifting the processing boundary: On-Farm Pulsed Electric Field Intervention (OFPI) for proactive bioburden reduction and functionalization of raw milk - Bing Yan; Lang-Hong Wang; Jin-Lin Cai; Xiao-Jun Zhang; Cai-Yun Wang; Jian Li; Rui Wang; Xin-An Zeng; Jian He (Trends in Food Science & Technology, 2026)

Unveiling the molecular diversity of toxins and non-toxins in the medicinal sea snake Hydrophis cyanocinctus through integrated venomics investigation - Jiayi Lin; Zhaoran Yu; Yue Cheng; Sheng Han; Ruiwei Ye; Dandan Yang; Xiawen Dang; Haorui Dai; Zhiping Zhao; Yonghong Zhou; Yiming Lu; An Li (Toxicon, 2026)

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Precise nanodelivery of screened compounds alleviates sepsis-associated encephalopathy by targeting microglial ANXA2 - Daoyi Lin; Yuan Huang; Shuyan Wu; Zefu Li; Hanhao Dai; Fei Gao; Danfeng Wang; Maokai Xu; Ziqi An; Xinmu Li; Peng Ye; Yingjie Chen; et al. (Science Bulletin, 2026)

Seasonal variation of fish biodiversity in Xisha Islands based on dual-marker eDNA metabarcoding - Shengming Deng; Yuguo Ye; Min Liu; Bai-an Lin; Chengdan Ma; Yifeng Xu; Yongcan Zhou; Shifeng Wang; Weiliang Guo; Huilong Ou; Xiang Zhang; Jianlong Li (Marine Environmental Research, 2026)

Engineering an amino-modified MOF@COF interface to construct a light-responsive oxidase-like nanozyme for rapid total antioxidant capacity assay in foods - Yanhui Feng; An Xu; Huan Li; Xiumei Lin; Hongxu Guo (Food Chemistry, 2026)

Defect engineering in conductive MOFs: A strategy for high-performance paraquat electrochemical sensing - Xiao-Qin Li; Hao Ma; Deng-Yue Ma; Tiao-Bin Zhao; Lin-An Cao (Chemical Engineering Journal, 2026)

Formation gassing and high-temperature cycling of 5 Ah batteries with lithium-rich ferrite lithium as pre-lithiation reagent - Youzhi Song; Yun Gao; Fuqiang An; Boyuan Lin; Yuhan Wang; Xiaoyu Li; Yiding Li; Xiaoguang Yang; Jiuchun Jiang; Wenwei Wang (Chemical Engineering Journal, 2026)

Boosting electron transfer for high-performance microbial fuel cell with Cu2O-modified cathodes: Regulated pathway, reduced impedance, and remodelled microbial functions - Jinyan Guo; Hongxue An; Yingzhen Li; Lin Yue; Yankai Guo; Jing Lian (Bioresource Technology, 2026)

Proteomic comparison of human neural cell-derived extracellular vesicles and parental cells from Alzheimer’s disease and cognitively normal individuals - Jia-Yan Xin; Jie Liu; Hao-Min Dong; Hai-Lun Yu; Zhong-Song Xiao; Jian-Ni Hu; Qiu Jiang; Yu-Peng Zhu; Lin Feng; Yun Feng; Yu-Juan Jia; Zi-Yu Yuan; et al. (Science China Life Sciences, 2026)

Short anti-aging peptides from edible microalgae using a multi-targets virtual screening strategy combined with Caenorhabditis elegans model - Yan-yan Yuan; Xin Li; Ming-hui Han; Xue An; Yong-Qiang Lin; Hong-Bing Liu (Food Research International, 2026)

Engineering over-oxidized cu on CNTs for sensitive non-enzymatic glucose sensing and energy applications - Songxin Zhong; Rida Li; Hui Chen; Chao Xiao; Yining Lan; Qi-an Chen; Jian Li; Changqiang Feng; Shizhan Li; Hengchan Qi; Chi Gong; Zukun He; et al. (Chemical Engineering Journal, 2026)

Mechanically robust and electrolyte-stable 2D MOF-based nanocomposite membrane with rich low-resistance highways for high-performance osmotic energy harvesting - Chia-An Lung; Guang Hui Teoh; Wen-Hung Lin; Kalon Gopinadhan; Soorathep Kheawhom; Li-Hsien Yeh (Chemical Engineering Journal, 2026)

Breaking the sensitivity barrier in ELISA: A molecularly engineered peptide nanointerface achieves ultrasensitive detection of zearalenone - Zijun Yang; Zhiwei Liu; Zhongqi Lin; Wenjuan Xu; Xiu'an Duan; Zhenlin Xu; Xiangmei Li (Analytica Chimica Acta, 2026)

Bacillus subtilis modulates the intestinal microbiome and metabolism to promote growth and disease resistance in Micropterus salmoides - Meiyu Li; Wengen Zhu; Shuhui Niu; Xingxing An; Lin Chen; Houxiong He; Yaohua Wang; Song Zhang; Yong Yang; Qirui Li; Huanping Liu; Shuhan Zhang; et al. (Aquaculture, 2026)

Non-equilibrium criticality-enhanced quantum sensing with superconducting qubits - Hao Li; Yaoling Yang; Yun-Hao Shi; Zheng-An Wang; Ziting Wang; Jintao Li; Yipeng Zhang; Kui Zhao; Yueshan Xu; Cheng-Lin Deng; Yu Liu; Wei-Guo Ma; et al. (Science Bulletin, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Association of dietary intake of copper and zinc with systemic inflammation: A cross-sectional study integrating machine learning - Xuefei Zhang; Yuqing Deng; Huan Su; Xueran Huang; Yongfen Gao; Zhuangzhuang An; Zouyan He; Dan Li; Haiying Zhang; Rui Lin (Journal of Trace Elements in Medicine and Biology, 2026)

Polystyrene microplastics disrupt the blood-testis barrier via CEBPB-driven lysosomal autophagy and induce ferroptosis-like injury in human sperm, compromising embryo development - Man Wu; Lei Li; Tianxin Zhao; Yuling Mao; Jiajing Lin; Xiaomin Li; Yanling Bai; Feixue Han; Shuyan Chen; Tianwen Peng; Chen Liao; Xin Ye; et al. (Journal of Hazardous Materials, 2026)

Liquid-phase hydrogenation of benzaldehyde to benzyl alcohol over NiCoAl‑R catalysts: Synergistic metal–metal oxide interfaces for enhanced catalytic performance - Lingmei Yang; An Wei; Ru kuan Liu; Guo ling Zhang; Bing Han; Baining Lin; Lianhua Li (Journal of Environmental Chemical Engineering, 2026)

Melatonin safeguards embryo and blastoid development against oxybenzone toxicity via a mitochondrial-linked NAD+ and glucose metabolic axis - Yuying Xiong; Haiying Zhu; Han Xie; Yunqi Wu; Ruojin Shi; Xueling Zhang; Lin Zhu; Yiwen Wang; Ke Zhong; Lei Li; Yaming Meng; Minyu Xie; et al. (Environmental Pollution, 2026)

Tailored self-assembled molecule for efficient charge extraction and enhanced crystallization in wide-bandgap perovskite solar cells - Haojun Hu; Xianglang Sun; Xuke Yang; Zongbao Li; Peiyan Zhang; Xinyu Yu; Shi'ang Li; Zifan Lin; Dayu Liu; Ziyang He; Chuyun Deng; Longhui Zeng; et al. (Chemical Engineering Journal, 2026)

Multi-stage synthetic microbial consortia outperform single-stage augmentation by remodeling metabolism and mediating function-stability trade-off in anaerobic digestion - Miaomiao An; Jiarui Yu; Xianghao Lin; Yanjuan Lu; Xiaoxu Li; Jinling He; Guozhu Zhao (Bioresource Technology, 2026)

Research on Production–Living–Ecological Space recognition and evolutionary characteristics based on time-series Landsat images and POIs in a coastal economic and technological development zone - Yanghua Zhang; Bin Liu; Li Zhang; Lingxiao An; Weipeng Lin; Yiran Yan (International Journal of Remote Sensing, 2026)

A stimulating effect induced by Bisphenol A bis (diphenylphosphate) in HepG2 cells via vascular endothelial growth factor (VEGF)/VEGF receptor axis - Jing An; Yuting Yi; Na Li; Miao Lin; Yufang Zhong; Guofa Ren; Yu Shang (Toxicology Letters, 2026)

Description of a novel organic acid-degrading bacterium with biotechnological potential, Denitratimonas organivorans sp. nov., genomic assessment of the genus Denitratimonas, and proposal of a new species Denitratimonas yunnanensis sp. nov. named following the rules of the SeqCode - Miaomiao An; Rongrong Wang; Ruina Liang; Xianghao Lin; Xiaoxu Li; Yanjuan Lu; Guozhu Zhao (Systematic and Applied Microbiology, 2026)

Nanofiber engineering of covalent organic frameworks via monomer–solvent synergy for high-efficiency uranium capture - Xiao-yi Tang; Qun-yan Wu; Yi-chen Huang; Peng-fei An; Lin Wang; Ji-pan Yu; Shu-sen Chen; Zi-jie Li; Li-yong Yuan; Wang-suo Wu; Zhi-fang Chai; Wei-qun Shi (Journal of Hazardous Materials, 2026)

Boosting multi-heavy metal sequestration in king grass: Unveiling the role of Serendipita indica symbiosis and the key root exudate GABA - Yali Duan; Jialiang Luo; Miaomiao Wang; Dong Li; Huiping Feng; Li Lin; Qianli An; Shunqing Xu; Zhiqiang Zhu (Journal of Environmental Sciences, 2026)

Ce-Fe bimetallic zeolite-imidazolate framework catalyzed ozonation for enhanced tetracycline degradation: synergistic electron transfer and multi-radical reaction pathways - Lin Yue; Shiqi Xing; Mengfei Wang; Hongxue An; Yunlong Yao; Yuxuan Li; Jing Lian (Environmental Research, 2026)

High-sensitivity and ultra-wide-range flexible piezoresistive sensor with surface microsphere and gradient cell structure for human gait correction - Xiangfang Peng; Shengguo Gu; Wen Xiao; Yuhuan Lin; Shulei Wu; Shuai Wang; Bin Tan; Haoyang Mi; Suiyi Li; Zhixiang Cui; Yongchao Xu; Feifan Yi; et al. (Chemical Engineering Journal, 2026)

Bridging accelerated cell-level degradation to module-relevant failure mechanisms in TOPCon solar cells and modules - Xinyuan Wu; Wei Wu; Weiguang Yang; Yan Zhang; Jiexi Fu; Xutao Wang; Jing Yuan; Jianjun Nie; Zhencong Qiao; Chao An; Feng Li; Lin Lv; et al. (Chemical Engineering Journal, 2026)

Hydroxylamine enhances the iron double-cycle system to improve the removal efficiency of norfloxacin via Fe3O4@N-rGO/PMS system - Lingzi Fu; Chao Wang; Aiguo Lin; Zhangbin Pan; Bin Wang; Li'’an Hou (Chemical Engineering Journal, 2026)

A high-performance bimodal sub-nanoporous polyelectrolyte complex membrane for organic solvent nanofiltration constructed by MOF-reinforced nano-unit - Hui-Qian Huo; Bing-Xin Gu; Jin-Lin Wang; Jia-Chen Zhang; Kai Zhang; Ming-Jie Yin; Yan-Li Ji; Quan-Fu An (Chemical Engineering Journal, 2026)

OH-initiated aqueous oxidation of methylglyoxal: Implications for organic acid and oligomer formation - Jiaxin Wang; Ying Chen; Wenjie Gao; Sihao Lin; Wenjian Li; Yongpeng Ji; Xiaolei Zhao; Yanpeng Gao; Yuemeng Ji; Taicheng An (Atmospheric Environment, 2026)

Comprehensive understanding of new particle formation in China through advanced modeling - Jiewen Shen; Bin Zhao; An Ning; Wei Nie; Chao Yan; Yuyang Li; Runlong Cai; Alfonso Saiz-Lopez; Manish Shrivastava; Biwu Chu; Da Gao; Nanna Myllys; et al. (Science Bulletin, 2026)

High-frequency observation reveals the impacts of suspended sediment and hysteresis effect on water quality in soil erosion areas - Yongqiang Lin; Zhixiang Sun; Jiacheng Li; Jiayu Jiang; Qingqing Zuo; Tengyu Zhang; Kun An; Zhenyao Shen; Lei Chen (Journal of Hydrology, 2026)

Screening, risk assessment, and rapid detection of mycotoxins in edible herbs based on UPLC-MS/MS and FT-NIR - Kangnan Liu; Ling Fang; Yaling An; Zijun Tang; Wenjie Zhao; Chunqian Song; Lin Feng; Xiaokang Liu; Zhenwei Li; Daidi Zhang; De-an Guo (Food Research International, 2026)

Mechanisms of phosphorus release from coastal sediments driven by organic matter enrichment at high nitrogen concentrations - Chun-Pu Zhao; An-Hao Wang; Ying Zeng; Wen-Hao Yin; Cheng Luo; Shi-Xia Liu; Miao Liu; Hai-Jun Wang; Xiao-Wen Li; Ji-Lin Xu; Shuo-Nan Ma (Marine Pollution Bulletin, 2026)

Intercropping significantly elevates carbon sequestration by mitigating the decline in soil total carbon caused by excessive phosphorus-application - Chuan-Lin Xiao; Ran An; Jiu-Dong Zhang; Yi Xing; Xing-Guo Bao; Rui-Peng Yu; Hans Lambers; Xiang Wang; Long Li (Soil and Tillage Research, 2026)

Unified quasi-solid electrolyte design for coupled stabilization of Zn anode and I2 cathode in aqueous Zn-I2 batteries - Meng’an Wang; Tao Li; Shicong Zhang; Hexian Ma; Yang Xu; Yi Shen; Chenyu Wei; Tao Zhang; Tianquan Lin (Science Bulletin, 2026)

Detecting global ocean subsurface density change with high-resolution via dual-task densely-former - Hua Su; Weiqi Xie; Luping You; Sihui Li; Dian Lin; An Wang (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Fabrication of synergistic photocatalytic–photothermal nanofibrous membrane for photo-assisted membrane distillation process - Xiaochan An; Jinhui Zhang; Jingjiao Li; Dandan Ma; Lin Cheng; Fenghui Chen; Jinsong He (Desalination, 2026)

High-performance composite solid electrolyte with elevated ionic liquid and high-dielectric high-entropy oxide in poly(vinylidene fluoride-co-hexafluoropropylene) for advanced lithium-ion batteries - Wen-Hsuan Lu; Yen-Shuo Huang; Yen-Lin Chen; Yi-Hsuan Tseng; Jue-Hua Pan; You-Yi Li; Ying-Da Luo; Chun-Han Kuo; Chih-Ping Tan; Ruey-An Doong; Ho-Hsiu Chou; Ai-Yin Wang; et al. (Chemical Engineering Journal, 2026)

Preferential N2-transport thin-film composite membrane for energy-efficient CO2 capture - Jin-Lin Wang; Cheng-Gang Jin; Hui-Qian Huo; Bing-Xin Gu; Yue Li; Wen-Hai Zhang; Ming-Jie Yin; Quan-Fu An (Chemical Engineering Journal, 2026)

Synergistic co-preintercalation of nickel and aluminum ions into vanadium oxide hydrate as positive electrode material in ultrahigh-rate and high-capacity aqueous zinc-ion batteries - Hung-Lin Chen; Tsung-Yi Chen; En-Hao Li; Yen-Lin Chen; Wen-Hsuan Lu; Hsu-Chen Cheng; Shu-Yu Chen; Jue-Hua Pan; Hsiang-Jung Chen; Syuan-Cen Lin; Ruey-An Doong; Sanna Gull; et al. (Chemical Engineering Journal, 2026)

First evidence of CP violation in beauty baryon to charmonium decays - R. Aaij; A.S.W. Abdelmotteleb; C. Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2026)

Two new naphthopyrones and a new prenylisoflavone from Berchemia lineata - Ling Li; Lin Feng; Lihua Peng; Weilin Qiao; Wei Li; De-an Guo (Phytochemistry Letters, 2026)

Decoupled intracontinental convergence between the South Tian Shan and northern Tarim Basin since the Neogene: Constraints from stratigraphy and detrital zircon U Pb geochronology of the Alparlek section - Kaixuan An; Jialun Huang; Xiubin Lin; Hanlin Chen; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Jinkai Xia; Xiaogan Cheng; Fengqi Zhang; Ziyi Wang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Topography and rural settlement control the evolution of sloping cropland toward diversity—evidence from the Three Gorges Reservoir Area over half a century - Xinyi Sun; Wenxin Zhao; Yangbing Li; Ying Huang; Lin Liu; Jing'an Shao (Journal of Cleaner Production, 2026)

Multi-scale assessment of energy transition and emission patterns in industrial coastal regions - Ying Teng; Mingkun Bai; Xiran Lin; Jiajie Li; Tao Zhang; Shuyang Liu; Senyou An; Liangbin Xu; Pengfei Wang; Songbai Han; Jinlong Zhu; Jianbo Zhu; et al. (Fuel, 2026)

Zero-energy, capillarity-gravity self-filtration system: A sustainable and ultra-low cost solution for high-efficiency microalgae removal - Haochuan Lin; Junjie Yang; Yuqin An; Mo Dong; Zupei Wang; Yiqi Tang; Huanhuan Tang; Hong Yao; Xinyang Li; Wen Zhang (Chemical Engineering Journal, 2026)

Benzo[c]chromene-based light-emitting conjugated polymer for high performance deep-blue PLEDs - Hong Ren; Zhiyang Sun; Xiang An; Qian Wu; Xinyu Du; Xiaoqi Guo; Wenyu Chen; Mengyuan Li; Jiabin Liu; Dunliang He; Ning Sun; Lubing Bai; et al. (Chemical Engineering Journal, 2026)

Design of asymmetric combined flow-guiding valve core structure in hydraulic spool valve - Zhao-tong Wang; Wen-qing Li; Xu-han Wang; Tong An; Zhen-hao Lin; Zhi-jiang Jin; Jin-yuan Qian (Annals of Nuclear Energy, 2026)

Evaluation of MarR-deleted Streptococcus agalactiae as a live-attenuated vaccine candidate for Nile Tilapia (Oreochromis niloticus) - Tian-Yu Ma; Feng-yang Li; Chang-Song Wu; Jian-Hao Lin; Ming Chen; Yong-An Zhang; Hui Zeng (Aquaculture, 2026)

Effect of extrusion parameters on the quality of extruded reconstituted konjac glucomannan Rice - Rui Lai; Jie Liu; Hanxiao Qin; Qing Li; Yong Chen; Wenxuan Pan; Jikai Zhao; Qing Huang; Hongzhou An; Qian Lin; Yanru Li (Food Chemistry, 2026)

Alterations in Gut Microbiota and their Association with Colonic Permeability and Inflammation in LPS-induced Sepsis Mice - Mengke Zhang; Yanyan Shu; Jingnan Yang; Sen Sang; Xiaoming Liu; Yuxia Li; Changjiang Qin; Lei An; Xuhong Lin (Current Microbiology, 2026)

Excavation-induced soil disturbance assessment of soft clay behind the diaphragm wall - Yan-Guo Zhou; Mu-Zhi Li; Yu Tian; Jun-Neng Ye; Wei-An Lin; Yun-Min Chen (Tunnelling and Underground Space Technology, 2025)

Biocontrol efficiency and potential mechanism of dimethyl trisulfide against postharvest Diplodia stem-end rot in pummelo (Citrus maxima) - Yankun Lin; Shun Feng; Haijin Cai; Haibo Wang; Xiuli Zhang; Fangfang Wu; Shuoyu An; Xinguo Li (Postharvest Biology and Technology, 2025)

Perinatal maternal lead exposure induces intergenerational neurotoxicity via mitochondrial dysfunction and mediation by perturbation of thyroid function - Lin Zhang; An-Xin Lu; Ling Li; Qian Wei; Yin Lin; Jun-Xia Liu; Li Ma; Ren-Tong Chen; Bin Luo; Chong-Huai Yan (Journal of Hazardous Materials, 2025)

Multiomics and machine learning unveil root exudate-microbiota interactions for cadmium control in rice - Ye Li; Jie Hou; Mengqi Liu; Zhaolin Du; Hongan Chen; Guofei Liu; Yajun Wang; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Environmental Management, 2025)

Multi-omics analysis reveals PkNF-YA7a as a transcriptional activator that promotes glycerolipid biosynthesis in Pinus koraiensis seeds - Zeyu An; Yuxin Song; He Zhang; Xin Wang; Dongran Zheng; Peitian Yu; Yangxin Wang; Wenqian Hao; Lin Wu; Yang Zhang; Hailong Shen; Yuhua Li; et al. (Food Chemistry, 2025)

High-yield hydrogen from fluidized-bed biomass gasification via waste-derived anti-sintering composite sorbents - Baokun Li; Liangliang An; Shaoxiang Pu; Aoyang Zhang; Lin Li; Lunbo Duan; Ryang-Gyoon Kim; Xing Zhu; Hua Wang; Dongfang Li (Chemical Engineering Journal, 2025)

A carboxymethyl chitosan/oxidized alginate hydrogel with controlled fullerenol release accelerates diabetic wound healing through cellular senescence reprogramming - Ze-Bang Du; Qi Yuan; Ke-Jian Ni; Jie He; Jia-Shen Wu; Hai-Yan Huang; Yan-Yan Zhou; Xiao-Qing Li; Chang-Feng Zhu; Xiao-Xuan Chen; Li-Li Pan; Ran An; et al. (Chemical Engineering Journal, 2025)

Mountain ecosystem health response to landscape pattern in the Three Gorges Reservoir Area, China - Lin Liu; Qingrong Wang; Yangbing Li; Jing’an Shao; Ying Huang (CATENA, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Coplanar DCA-based hypofractionated stereotactic radiotherapy for very small brain metastasis from non-small cell lung cancer: treatment planning comparison with coplanar VMAT and preliminary clinical outcome - Shipai Zhu; An Li; Jia Liu; Qin Deng; Qingfang Li; Jialu Lai; Lin Zhou (Physical and Engineering Sciences in Medicine, 2025)

Testing and modeling of chemically induced changes in mechanical characteristics of cement-stabilized sensitive marine clays - Yang An; Yubin Li; Can Yang; Zhuoma Yangjin; Lin Yuan (Marine Georesources & Geotechnology, 2025)

Stability of RL-modified n-FeS and its mechanisms for Cr(VI) removal efficiency - Kaipian Shi; Junfeng An; Lin Xu; Li Yin; Chunqing Peng; Yong Zhang; Shiyin Li; Lixiao Ni (Journal of Water Process Engineering, 2025)

Hydrocarbon organic conjugated skeleton with multi-sites functionalization for non-doped ultraviolet organic light-emitting diodes with CIEy = 0.029 - Jing Yang; Jingli Lou; Mingjian Ni; Zhiqiang Zhuo; Hao Li; Xiang An; Ning Sun; Mengyuan Li; Xuehua Ding; Lizhi Wang; Man Xu; Xueqin Ran; et al. (Chemical Engineering Journal, 2025)

COMPERA 2.0 risk stratification in patients with severe aortic stenosis: implication for group 2 pulmonary hypertension - Zongye Cai; Xinrui Qi; Dao Zhou; Hanyi Dai; Abuduwufuer Yidilisi; Ming Zhong; Lin Deng; Yuchao Guo; Jiaqi Fan; Qifeng Zhu; Yuxin He; Cheng Li; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Inspecting urban transit-oriented development from the perspective of human activity: A case study of Xi'an, China - Jiayu Liu; Xiping Yang; Lin Luo; Junyi Li; Hongfei Chen; Rui An; Jiyuan Li (Journal of Transport Geography, 2025)

Halogenated flame retardants in the sediments of the lower Great Lakes and region-wide discoveries - Tian Lin; Shanshan Zhou; Huan He; Jiehong Guo; Neil C. Sturchio; Karl J. Rockne; John P. Giesy; An Li (Journal of Hazardous Materials, 2025)

A machine learning and counterfactual reasoning-integrated decision framework for cadmium remediation: Predictive optimization and cost-benefit analysis driven by iron plaque regulation - Ye Li; Jie Hou; Mengqi Liu; Ruilin Li; Zhaolin Du; Yanpo Yao; Peizhe Sun; Lin Zhao; Yi An (Journal of Hazardous Materials, 2025)

Ceramic fiber aerogels based flexible solar steam generators enabling efficient thermal localization and high salt resistance - Yun Jiang; Yumin Liu; Lin Li; Zhibin Li; Pengzhang Li; Xianshu Qiao; Wenyan Zhao; Chuanjin Tian; Weiwei Sun; Yanhao Dong; Zhipeng Xie; Chang-An Wang (Desalination, 2025)

Halogen-sulfur synergy in benzodithiophene-benzodithienedione conjugated polymers: Molecular design of high-performance photoelectrodes for metal anti-corrosion - Rui Ding; Jin-ying Li; Yi-wen Zhang; Hao-han Cao; Xiao Liu; Yu-han Wang; Ming-di Lei; Yu-lin Zhang; An-lan Ji; Yu-chen Zhang; Jie Liu; Tai-jiang Gui; et al. (Chemical Engineering Journal, 2025)

Flexible chain-engineered conjugated polymers with phosphonic acid anchors for synergistic photocatalysis-adsorption uranium extraction - Yuanping Jiang; Feng Wang; Junshuo An; Xingfang Yu; Menghan Cao; Guohang He; Danning Xu; Jiajian Yang; Kai Zhang; Yunxiu Zhang; Lin Xu; Zuojia Li; et al. (Chemical Engineering Journal, 2025)

Critical factors and cost estimation for the immobilization of cadmium-contaminated paddy fields for rice safety - Shuqi Li; Dasong Lin; Lili Huo; Bo Wu; Lixia Sun; Yi An; Yuqing Xia (Journal of Soils and Sediments, 2025)

Distribution pattern of cetaceans in the northern South China Sea based on visual surveys and environmental DNA metabarcoding - Shengming Deng; Xiang Zhang; Min Liu; Bai‐An Lin; Yongcan Zhou; Mingming Liu; Wenzhi Lin; Mingli Lin; Lijun Dong; Hui Kang; Binshuai Liu; Shenglan Chen; et al. (Conservation Biology, 2025)
The South China Sea (SCS) is vital habitat and potential nursery and feeding grounds for large cetaceans, such as the sperm whale ( Physeter macrocephalus ), making understanding of the temporal and spatial patterns of cetaceans in this region essential. We examined the accuracy of environmental DNA (eDNA) in detecting cetacean species diversity and determine the spatial and temporal distribution of cetaceans in the northern SCS. We conducted 5 ship‐based visual surveys for cetaceans in 3 summers and 2 springs from 2020 to 2023 and used eDNA metabarcoding to determine the relative abundance and spatial and temporal distribution of cetaceans in offshore and abyssal areas of the northern SCS. We detected 18 cetacean species through visual observations and eDNA metabarcoding. Both methods identified 12 species in common. Cetaceans’ presence varied temporally. We detected 7 species in the springs and 17 species in the summers. Expedition route design, meteorological conditions, and sea conditions between the 2 seasons partly explained the seasonal differences. The species of Ziphiidae, Physeteridae, and Kogiidae tended to occupy regions with high bathymetric drop gradients, particularly those situated on continental slopes and seamounts. The Delphinidae were more widely distributed and relatively more abundant. Of the cetaceans successfully identified by eDNA metabarcoding, species with relatively large group sizes and that were relatively close to the sampling sites tended to be more easily detected. Our results provide new information on the relative abundance and spatial and temporal distribution of cetaceans and indicate that eDNA techniques can provide additional information and serve as a complementary tool for cetacean monitoring and conservation.

Integrin CD11b Alleviates Cerebral Ischemia/Reperfusion Injury via a Mechanism Involving Microglia/Macrophage Polarization - Gui-Nan Jiang; Qiu-Yue Lin; Xiang-Bo An; Wei-Jia Yu; Jie Bai; Xin Yu; Feng Wang; Hui-Hua Li (Journal of Molecular Neuroscience, 2025)

2-Arylbenzofurans from the stems and leaves of Artocarpus tonkinensis and their potential antiproliferative activities - Jia-Ming Guo; Lin-Xuan Li; Xin-Yi Li; Tian-Yu Wang; En-Ning Zhu; An-Jiao Wu; Shu-Ri Li; Hui- Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2025)

Deciphering the venom components of Sea snakes: Integrating dual proteomic techniques to uncover the bioactive potential of Hydrophis curtus - Yingying Li; Haorui Dai; Zhiping Zhao; Ruiwei Ye; Sheng Han; Dandan Yang; Hanyu Pan; Jiayi Lin; Xiawen Dang; Yue Cheng; Zhaoran Yu; An Li; et al. (Toxicon, 2025)

Detrital zircon U Pb geochronology of the Cenozoic succession in the southern Tarim Basin: Implications for the northward expansion of the West Kunlun Orogen and the evolution of intracontinental convergence in the northwestern Tibetan Plateau - Chunyang Li; Kaixuan An; Xiubin Lin; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Shujun Liang; Xiaochun Wei; Yang Qu; Xinyue Zhao; Jialun Huang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Strontium diorthovanadate anode for fast-charging lithium-ion battery with low redox potential - Xiaolei Li; Shuangdui Wu; Jian Su; Jing Zhang; Xuguang An; Weitang Yao; Hongli Sun; Borong Lin; Qingquan Kong (Chemical Engineering Journal, 2025)

Block copolymer architectures with poly(ε-caprolactone) for modulating interactions to enhance selectivity and stability of semiconducting single-walled carbon nanotube dispersions - Mei-Nung Chen; Rin Iwasaki; Mayoh Ashiya; Haoyu Zhao; Qi-An Hong; Yen-Ting Li; Kai-Lin Chen; Maina Moses Mburu; Wei-Ting Li; Xiaodan Gu; Wei-Hung Chiang; Takuya Isono; et al. (Chemical Engineering Journal, 2025)

Potential prognostic biomarker of OSBPL10 in pan-cancer associated with immune infiltration - Jiapeng Qi; Kun Yu; Bei Liu; Yan Wang; Wei Wang; Ran An; Chaojun Wang; Na Li; Dongqian Xu; Lin Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Cadmium exposure causes trophoblast abnormal syncytization and endocrine dysfunction in preeclampsia - Weilong Lin; Xuemeng Li; Xiangyou An; Jiancai Yin; Ziyan Zhao; Xiaorui Yan; Rong Xu; Baojing Zhao; Xue Du; Huiru Cheng; Zhen Yu; Yuanyuan Yang (Reproductive Toxicology, 2025)

Harmonizing stakeholder interests in urban renewal: A novel planning approach using explainable machine learning and spatial optimization - Chuan Lin; Yilun Liu; Zhongyou Yuan; Hongmei Wang; Guang Li; Zegen Zhou; Han Wang; Xinyue An (Land Use Policy, 2025)

SpecDETR: A transformer-based hyperspectral point object detection network - Zhaoxu Li; Wei An; Gaowei Guo; Longguang Wang; Yingqian Wang; Zaiping Lin (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Unlocking the healing power of Jinhua white tea fermented by Eurotium cristatum using the unique “flowering” technology: A promising ally against inflammatory bowel disease - Yong Lin; Xirui Zhou; Silin Xie; Jian-an Huang; Jie Li; Yanyan Yao; Maiquan Li; Jiahui Bo; Lizheng Xiao; Zhonghua Liu; Wei Quan (Food Research International, 2025)

Combining the life cycle model and corrosion model to analyze the impact of corrosion on carbon emissions of steel pipelines - An Yan; Ying Xiao; Hongyang Ren; Bing Lin; Hailong Zhang; Yingying Wang; Xi Li; Bing Wang; Junlei Tang (Environmental Impact Assessment Review, 2025)

Changes in soil organic carbon and its forms in recovering alpine meadows of various lengths in relation to altitude - Chunying Lin; Xilai Li; Huafang Sun; Xiaoxue Su; Hongmei Li; Rongna Liu; Chengyi Li; Yonghui Hou; Shizhen Zhu; Di Yu; Liyan Zhang; Jiexia Li; et al. (CATENA, 2025)

CCN1 Is a Therapeutic Target for Reperfused Ischemic Brain Injury - Gilbert Aaron Lee; Yu-Wei Chang; Jing-Huei Lai; Tzu-Hao Chang; Shiu-Wen Huang; Chih‑Hao Yang; Ting-An Shen; Wan-Li Lin; Ying-Chieh Wu; Li-Wen Tseng; Sung-Hui Tseng; Yung-Chieh Chen; et al. (Translational Stroke Research, 2025)

Detrital Zircon U-Pb Age Analysis of Late Pliocene Deposits from the Lower Yangtze River, South China: Implications for Sedimentary Provenance and Evolution of the Yangtze River - Xu Lin; Yuxuan Pang; Chang’an Li; Jing Liu-Zeng; Marc Jolivet; Haijin Liu; Chengwei Hu; Xiaokang Chen (Journal of Earth Science, 2025)

Karst Trough Control of Solute Transport Processes at Two Karst Groundwater Flow Systems, Western Hubei, Central China - Yi’an Wang; Ruichao Zhao; Lin Ding; Shuai Xiong; Yin Li; Jianwei Bu; Wei Chen; Hong Zhou; Wei Liu (Journal of Earth Science, 2025)

Electronic state reconfiguration of NiMoCox boosts electrocatalytic upcycling of polyethylene terephthalate plastic wastes for simultaneous production of formate and green hydrogen - Shaofeng Wang; Shuaidong Li; Yutong Li; Yue Xu; Zhaomeng Wu; Yingjian He; Yongwei Zhao; Zheer An; Ying Lan; Yanxiao Hu; Jingzi Zhang; Yan Huang; et al. (Chemical Engineering Journal, 2025)

Correlation study of 5-HT in brain with cognitive function and anxious-like behavior in APP/PS1 transgene mice - Li Yuan; Linshan An; Rui Xie; Jiahong Cai; Dong Li; Xiaorong Chen; Wenjing Guo; Yinran Lin; Chunjing Zhu; Yongli Chang; Kunbo Wang; Weina Han; et al. (Sleep and Biological Rhythms, 2025)

Modeling and mechanistic understanding of vertical dissolved methane transport in integrated vertical flow constructed wetlands (IVCWs) - Ru Xue; Ke Zhang; Xiaoling Liu; Bing Jiang; Hongbing Luo; Mei Li; You Mo; Cheng Liu; Lin Li; Wei Chen; Lin Cheng; Jia Chen; et al. (Journal of Water Process Engineering, 2025)

Geochemistry, geochronology and Fe-Mg-S isotopic composition of the Liaoshang gold deposit, Jiaodong Peninsula, China: Implications for ore-forming processes and mineral exploration - Yuan-lin Chen; Huan Li; Shang-yi Gu; Scott A. Whattam; Chao-yang Zheng; Li-gong Wang; Da-dou Li; Liu-an Duan (Journal of Geochemical Exploration, 2025)

Atomevo-odor: A database for understanding olfactory receptor-odorant pairs with multi-artificial intelligence methods - Heng-Yun Zhao; Si-Min Xu; Si-Nuo Xie; Wan-Lin Ye; Jian Li; Lang-Hong Wang; Shi-Lin Cao; Jun-Hu Cheng; Xin-An Zeng; Ji Ma (Food Chemistry, 2025)

The role of electroactive biofilms in enhanced para-chlorophenol transformation collaborated with biosynthetic palladium nanoparticles - Shaofeng Zhou; Yanjing Li; Shan Yang; Lizhou Lin; Tongchu Deng; Cuifen Gan; Wenwen An; Meiying Xu (Environmental Pollution, 2025)

Corrigendum to “Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration” [Chem. Eng. J. 497 (2024) 154433] - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2025)

Characteristics of Humic Acid–Iron Colloid Stability and Its Mechanism of Binding with As(III) - Junfeng An; Conghui Wang; Jia Yu; Kaipian Shi; Youru Yao; Jingyi Zhang; Chonghong Zhang; Yuesheng Lin; Shiyin Li (Bulletin of Environmental Contamination and Toxicology, 2025)

A 10-Year Dataset of Land Surface Observations for the Semi-Humid Alpine Grassland in the Source Region of the Yellow River - Xianhong Meng; Yu Zhang; Lunyu Shang; Shaoying Wang; Zhaoguo Li; Shihua Lyu; Yinhuan Ao; Siqiong Luo; Lijuan Wen; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2025)
The source region of the Yellow River, accounting for over 38% of its total runoff, is a critical catchment area, primarily characterized by alpine grasslands. In 2005, the Maqu land surface processes observational site was established to monitor climate, land surface dynamics, and hydrological variability in this region. Over a 10-year period (2010–19), an extensive observational dataset was compiled, now available to the scientific community. This dataset includes comprehensive details on site characteristics, instrumentation, and data processing methods, covering meteorological and radiative fluxes, energy exchanges, soil moisture dynamics, and heat transfer properties. The dataset is particularly valuable for researchers studying land surface processes, land–atmosphere interactions, and climate modeling, and may also benefit ecological, hydrological, and water resource studies. The report ends with a discussion on perspectives and challenges of continued observational monitoring in this region, focusing on issues such as cryosphere influences, complex topography, and ecological changes like the encroachment of weeds and scrubland.

Upper limit of ice content at the lunar south pole as revealed by the Earth-based SYISR–FAST bistatic radar system - Mingyuan Li; Jinghai Sun; Xin’an Yue; Honglei Lin; Zhiqing Chen; Feng Ding; Baiqi Ning; Yong Wei; Chi Wang; Peng Jiang (Science Bulletin, 2025)

Study of D s 1 ( 2460 ) + → D s + π + π - in B → D ‾ ( * ) D s + π + π - decays - R. Aaij; A.S.W. Abdelmotteleb; C.Abellan Beteta; F. Abudinén; T. Ackernley; A.A. Adefisoye; B. Adeva; M. Adinolfi; P. Adlarson; C. Agapopoulou; C.A. Aidala; Z. Ajaltouni; et al. (Science Bulletin, 2025)

Functional characterization of chemosensory proteins in three sympatric Tomicus bark beetles feeding on Pinus yunnanensis: Implication for the conservation and divergence of ligand-binding profiles - Lin-Mei Pu; Peng-Fei Wang; Yu-Yue Lu; An-Jin Yang; Li-Li Liu; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2025)

Development of an alkali-producing bioelectrochemical system for sewage-polluted seawater: nutrient removal, scalant mitigation, and resource recovery - Chao-Chin Chang; Chieh-Yun Wu; Jia-Zhe Jiang; Chen-An Hsu; Chang-Ping Yu; Yi-Li Lin (Journal of Water Process Engineering, 2025)

Regulation strategies of microplastics with different particle sizes on cadmium migration processes and toxicity in soil-pakchoi system - Qirui An; Na Zheng; Changcheng Chen; Xiaoqian Li; Yining Ji; Liyuan Peng; Zhifei Xiu; Qiuyan Lin (Journal of Hazardous Materials, 2025)

Research on combustion characteristics of new high energy composite materials − using tungsten powder as fuel and DAP-4 as oxidizer - Guangwei Xiao; Erhai An; Hua Fang; Xueli Zhang; Yingxin Tan; Lin Li; Peng Deng; Zhuoxin Fei; Xiong Cao (Fuel, 2025)

Fu brick tea supplementation ameliorates non-alcoholic fatty liver disease and associated endotoxemia via maintaining intestinal homeostasis and remodeling hepatic immune microenvironment - Gaolong Zuo; Menghua Li; Xiaoli Guo; Ling Wang; Yanyan Yao; Jian-an Huang; Zhonghua Liu; Yong Lin (Food Research International, 2025)

Enhanced uranium extraction from seawater using bifunctional-modified molecular sieves with high selectivity and adsorption capacity - Wen Guo; Zixin Lin; Kun Jiang; Hao Li; Xiangfeng Liang; Weizhong An; Huizhou Liu; Haiyan Luo; Haoyu Yao (Desalination, 2025)

Gastrodin Protects Neuronal Cells Against Oxidative Stress Through miRNA-125b-5p/Mamdc2 Axis - Lei Hu; Chao Lin; Renfu Li; Shouying Xu; Qiang Xu; Zihao An; Chao Tang (NeuroMolecular Medicine, 2025)

The impact of carbon emissions trading policy on low-carbon economic development in China: an empirical analysis based on the environmental triple effect - Yongkai Wang; Qiguang An; Ruoyu Wang; Yunpeng Ma; Lin Li (Environment, Development and Sustainability, 2025)

Solar evaporator coupled with strong/weak convection and its cascade utilization - Zhengtong Li; Jia-Han Zhang; Jing Zhang; Peng Yan; Tao Yang; Chao Yang; Peng Lin; Taotao Meng; Meng An; Yingtang Zhou; Xingtao Xu (Science Bulletin, 2025)

Long-term suppression of Microcystis aeruginosa by tannic acid: Risks of microcystin pollution and proteomic mechanisms - Li Yin; Kaipian Shi; Yu Yin; Yong Zhang; Lin Xu; Junfeng An; Chunqing Peng; Conghui Wang; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

Urinary metabolic alterations associated with occupational exposure to metals and polycyclic aromatic hydrocarbons based on non-target metabolomics - Ping Lu; Rujian He; Yingjun Wu; Bizhi Wu; Hailing Li; Chang He; Meiqing Lin; Mengmeng Wang; Wenwen Cai; Xiantao Shen; Guiying Li; Zhiguo Cao; et al. (Journal of Hazardous Materials, 2025)

Effect of tertiary amine carbon quantum dots incorporation on oil/water separation performance of membranes - Gabriel V. Carballo; Hsin-Yi Lin; Pei-Chen Chen; Hong-Li Yang; Rhoda B. Leron; Chi-Lan Li; Hui-An Tsai; Kueir-Rarn Lee (Journal of Environmental Chemical Engineering, 2025)

Single- and combined-heavy metals/metalloids exposures are associated with infertility in US women aged 20–44: NHANES 2013–2020 analysis - He-Bin Chi; Jia-Jia Tang; Xiao-Yuan Fan; Han-Wen Zhang; Feng Tang; Xian-Shu Lin; Bing-Rui Yang; Na Li; Jun Guo; Li-An-Sheng Wu; Qiu-Qi Huang; Yin-Yin Xia (Reproductive Toxicology, 2025)

Uncovering toxin production and molecular-level responses in Microcystis aeruginosa exposed to the flame retardant Tetrabromobisphenol A - Li Yin; Yu Yin; Lin Xu; Yong Zhang; Kaipian Shi; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Journal of Hazardous Materials, 2025)

Resistance and propulsion trade-offs induced by different morphologies: Insights for fish conservation - Lin Sun; Jia Li; Min Chen; ChingHao Yu; Ruidong An (Journal of Environmental Management, 2025)

Carbonyl-amine condensation coupled ozonolysis of dipropylamine and styrene: Decay kinetics, reaction mechanism, secondary organic aerosol formation and cytotoxicity - Wanying Li; Jiangyao Chen; Qinhao Lin; Yuemeng Ji; Taicheng An (Journal of Environmental Sciences, 2025)

The thermal decomposition and combustion properties of DAP-4/FG composite materials - Guangwei Xiao; Erhai An; Xueli Zhang; Yingxin Tan; Tengyue Song; Lin Li; Peng Deng; Xiong Cao (Fuel, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Production and evaluation of a bivalent adjuvant inactivated vaccine against infectious hematopoietic necrosis virus and infectious pancreatic necrosis virus - Zhen Zhang; Chunyan Guan; Jingzhuang Zhao; Jingnan Lin; Yizhi Shao; Linfang Li; Tongyan Lu; Peng Chen; Yong-An Zhang; Liming Xu (Aquaculture, 2025)

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

Enhancing indoor air quality and cardiopulmonary health in patients with asthma by photocatalytic oxidation and filters air cleaner - Jia Lin Zhang; Guan-Yu Liao; Hong-Yi Lin; Jie-An Xie; Wan-Chen Li; Huang-Chi Chen; Da Wei Wu; Huai-Lei Juan; Jia-Yu Kuo; Pei-Shih Chen (Journal of Hazardous Materials, 2025)

Mechanistic insights into the impact of calcium and magnesium ions on ferrous sulfide aggregation and reducing activity - Kaipian Shi; Li Yin; Junfeng An; Lin Xu; Chunqing Peng; Yong Zhang; Yuechun Zeng; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Chemical Engineering Journal, 2025)

Mitochondria-targeted delivery of zinc-coordinated resveratrol nanoparticles rescues the osteogenic potential of periodontal ligament stem cells compromised by inflammation for periodontal wound healing - Yu-Jie Tan; Xuan Li; Wen-Jie Zhang; Yu-Meng Cao; Jie-Kang Zou; Lin Jing; Dian Gan; Yu-Zhe Chen; Mei Xu; Ying An; Fa-Ming Chen; Xiao-Tao He; et al. (Chemical Engineering Journal, 2025)

Using chondroitin sulfate lithium hydrogel for diabetic bone regeneration via regulation of macrophage polarization - Chenci Xu; Weiqi Li; Jing Mao; Ziyang Liu; An Lao; Lixia Mao; Anqi Gu; Jiaqing Wu; Aili Shen; Kaili Lin; Jiaqiang Liu (Carbohydrate Polymers, 2025)

Correction to: Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2025)

Characterization and functional analysis of small heat shock protein gene HSP20.1 in Bombyx mandarina - Hui An; Jiaqi Ding; Enxi Chen; Ruonan Li; Mingjun Lin; Heying Qian; Guodong Zhao (International Journal of Tropical Insect Science, 2024)

Eicosatrienoic acid enhances the quality of in vitro matured porcine oocytes by reducing PRKN-mediated ubiquitination of CISD2 - Zhi-Yong An; Sheng-Zhong Han; Zhou-Yan Li; Shuang-Yan Chang; Xiu-Li Zhang; Gao-Jie Lu; Tuo Zhang; Biao-Hu Quan; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Research on antibiotic resistance genes in wild and artificially bred green turtles (Chelonia mydas) - Xin Niu; Liu Lin; Ting Zhang; Xiaoyu An; Yupei Li; Yangfei Yu; Meiling Hong; Haitao Shi; Li Ding (Science of The Total Environment, 2024)

Modification of gut and airway microbiota on ozone-induced airway inflammation - Fei Xu; Qiong Wu; Lin Yang; Han Sun; Juan Li; Zhen An; Huijun Li; Hui Wu; Jie Song; Wen Chen; Weidong Wu (Science of The Total Environment, 2024)

A metabolic roadmap of waxy corn flavor - Jingyun Luo; Chunmei He; Shijuan Yan; Chenglin Jiang; An Chen; Kun Li; Yongli Zhu; Songtao Gui; Ning Yang; Yingjie Xiao; Shenshen Wu; Fajun Zhang; et al. (Molecular Plant, 2024)

Tissue-specific distribution and fatty acid content of PFAS in the northern Bohai Sea fish: Risk-benefit assessment of legacy PFAS and emerging alternatives - Zhifei Xiu; Na Zheng; Qirui An; Changcheng Chen; Qiuyan Lin; Xiaoqian Li; Sujing Wang; Liyuan Peng; Yunyang Li; Huicheng Zhu; Siyu Sun; Shuai Wang (Journal of Hazardous Materials, 2024)

Membrane modification in enhancement of virus removal: A critical review - Jie Zeng; Peter Desmond; Huu Hao Ngo; Wei Lin; Xiao Liu; Bingsheng Liu; Guibai Li; An Ding (Journal of Environmental Sciences, 2024)

A highly specific two-photon fluorescent probe for real-time monitoring of acetylcholinesterase in neurogenic disorders in vivo - Weizhen An; Zhongxi Huang; Wei Jiang; Fangning Du; Chenfeng Xu; Qian Shen; Naidi Yang; Jia Zhou; Lin Li; Changmin Yu (Analytica Chimica Acta, 2024)

The Complete Mitochondrial Genome of Chilo infuscatellus (Lepidoptera: Pyralidae), and Related Phylogenetic Analysis - Jiequn Yi; Jianbai Liu; Yongkai Mao; Yinjie Cheng; Minjiang Lin; Hanliang Xu; Yuxing An; Jihu Li; Han Wu (Biochemical Genetics, 2024)

Beach erosion and typhoons reduce green turtle nesting grounds on the Xisha Islands, South China Sea - Ting Zhang; Chenglong Zhang; Yupei Li; Yangfei Yu; Xiaoyu An; Yongkang Jiang; Jichao Wang; Liu Lin; Hai-Tao Shi (Frontiers in Marine Science, 2024)
Introduction Sea turtles are ideal flagship and umbrella species for marine biodiversity conservation. The quality of nesting grounds is crucial for the successful reproduction of sea turtles, as it determines whether they can successfully nest and hatch. The Xisha Islands represent the largest remaining nesting grounds for green turtles in China. However, they face numerous threats and lack management guidelines for nesting ground restoration. Methods In this study, we continuously monitored the beach changes and coastal erosion on North Island, which is located in the northern region of the Xisha Islands, from 2019 to 2022. Results From 2020 to 2022, the beach area on North Island decreased annually by 11,800 m 2 , accounting for 24.39% of the beach area in 2020. The proportion of suitable nesting sand types (including coarse and medium sands) also decreased annually, with a reduction of 40–70% on the southern beach of North Island. The peak nesting period of green turtles on North Island coincides with the frequent occurrence of typhoons in the South China Sea, causing tidal surges that inundate green turtle nests, resulting in an average nest loss rate of 35.25%. Discussion Based on the above threats, it is recommended to promptly initiate habitat restoration in severely eroded areas of green turtle nesting grounds to prevent further declines in nesting area and quality. Additionally, measures such as nest relocation should be implemented to enhance green turtle reproductive success.

Synthesis of hydrothermal carbonation carbon with tunable photocatalytic performance for trimethoprim degradation using an ethanol-water co-solvent strategy: Influence of ethanol concentration - Jiashuai Hu; Jie Chen; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; Wei Chen; et al. (Journal of Cleaner Production, 2024)

Corrigendum to “Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the industrial revolution recorded by high-resolution stalagmites” [Global and Planetary Chang, 232 (2024) 104337] - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Pyrene-encapsulated light-emitting π-conjugated polymer with excellent ozone tolerance capacity for large-area and flexible ultra-deep-blue PLEDs with CIEy = 0.08 - Hao Li; Mengna Yu; Yang Li; Manman Luo; Jingyao Ma; Yahui Zhang; Yeyang Wang; Yunlong Zhang; Yan Ma; Lubing Bai; Qiujing Bao; Jiabin Gu; et al. (Chemical Engineering Journal, 2024)

Phthalate monoesters accumulation in residential indoor dust and influence factors - Qiuyan Lin; Na Zheng; Qirui An; Zhifei Xiu; Xiaoqian Li; Huicheng Zhu; Changcheng Chen; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

Synthesis of a novel double Z-scheme BiVO4/Cu2O/g-C3N4 sonocatalyst and research on sonocatalytic degradation of tetracycline - Yang-Cheng Liu; Ying-Di Ge; Hui-Li An; Wan-Ting Ju; Xin-Yi Zhou; Mei-Yi Xing; Yang Wang; Lin Zhang; Xin Wang; Liang Xu (Journal of Environmental Chemical Engineering, 2024)

Large-area and high-efficiency carbon nanotube/silicon heterojunction solar cells enabled by self-similar fiber electrodes and solid-state gel electrolytes - Xian-Gang Hu; Bingsheng Li; Yi-Ming Zhao; An-Ping Wu; Zhenhua Lin; Peng-Xiang Hou; Chang Liu; Yue Hao; Jingjing Chang (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

NaCe0.7FX:Gd0.1,Tb0.2 nanoscintillator as a new sonosensitizer for potentiating cancer sonodynamic-immune therapy - Luyao Liu; Yuqi Yang; Yan Wang; Tian Qiu; Xingrun Li; Jiayuan Lin; Jin Wang; Xianwen Wang; Yan An; Xiaoyan Zhong; Jianxiang Li; Liang Cheng (Chemical Engineering Journal, 2024)

Smart glucose-responsive hydrogel with ROS scavenging and homeostasis regulating properties for diabetic bone regeneration - Ziyang Liu; Jing Mao; Weiqi Li; Chenci Xu; An Lao; Airi Shin; Jiaqing Wu; Anqi Gu; Zhen Zhang; Lixia Mao; Kaili Lin; Jiaqiang Liu (Chemical Engineering Journal, 2024)

Concentration characteristics and emission estimates of major HCFCs and HFCs at three typical fluorochemical plants in China based on a Gaussian diffusion model - Zehua Liu; Jing Wu; Tengfei Ma; Minde An; Tong Ye; Xingchen Zhao; Mingzhu Li; Fan Wang; Mao Yuan; Dongmei Hu; Yueling Zhang; Lin Peng (Atmospheric Environment, 2024)

Amentoflavone Induces Ferroptosis to Alleviate Proliferation, Migration, Invasion and Inflammation in Rheumatoid Arthritis Fibroblast-like Synoviocytes by Inhibiting PIN1 - Yan Ma; Hongjun Lin; Yunman Li; Zhuoling An (Cell Biochemistry and Biophysics, 2024)

Healthy lifestyles ameliorate an increased risk of periodontitis associated with polycyclic aromatic hydrocarbons - An Li; Yuntao Chen; Mi Du; Ke Deng; Xin Cui; Chunhua Lin; Geerten-Has E. Tjakkes; Xiaodong Zhuang; Shixian Hu (Chemosphere, 2024)

MCT1-mediated transport of valeric acid promotes porcine preimplantation embryo development by improving mitochondrial function and inhibiting the autophagic AMPK-ULK1 pathway - Xiu-Li Zhang; Zhi-Yong An; Gao-Jie Lu; Tuo Zhang; Cheng-Wei Liu; Meng-Qi Liu; Qing-Xin Wei; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2024)

Carbon footprint of fresh sea cucumbers in China: Comparison of three aquaculture technologies - Lin Yang; Dong An; Yuhu Cui; Xuexiu Jia; Dong Yang; Wensheng Li; Yanliang Wang; Longjie Wu (Journal of Cleaner Production, 2024)

Epinephelus coioides Sec3 promotes Singapore grouper iridovirus infection by negatively regulates immune response - Yu-Rong Lei; Jia-Yang He; Xue-Mei Fu; Cui-Fen Huang; Yun-Xiang Lin; Li-Ling Dai; Zi-An Chen; Ze-Peng Zhang; Fu-Min Liu; Qi-Wei Qin; Hong-Yan Sun (Fish & Shellfish Immunology, 2024)

Early-onset and later-onset cancer: trends, risk factors, and prevention in Northern China - Tong Liu; Chen-An Liu; Qing-Song Zhang; Qi Zhang; Yi-Ming Wang; Meng-Meng Song; Shi-Qi Lin; Li Deng; Shou-Ling Wu; Han-Ping Shi (Science China Life Sciences, 2024)

Enhancement of beneficial microbiomes in plant–soil continuums through organic fertilization: Insights into the composition and multifunctionality - Wen-Jing Li; Xin-Yuan Zhou; Xin-Li An; Li-Juan Li; Chen-Shuo Lin; Hua Li; Hong-Zhe Li (Soil Ecology Letters, 2024)

High-value utilization of boron mud waste: preparation of magnesium oxysulfate cement after primary blank roasting and secondary (NH4)2SO4 roasting - Jing Wen; Hongyu Sui; Tao Jiang; Lin Li; Xinyu An (Process Safety and Environmental Protection, 2024)

Northward expansion of the West Kunlun orogenic belt during the Cenozoic and its implications for the evolution of the northwest Tibetan Plateau: Constraints from sediment dispersal patterns in the Buya Basin, China - Shujun Liang; Xiubin Lin; Chunyang Li; Xiaochun Wei; Yang Qu; Kaixuan An; Cai Chen; Xianzhang Yang; Yong Li; Liang Zhang; Jiangwei Shang; Li Li; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

New simple method for calculating large-strain consolidation settlement of layered soft soils with horizontal drains and vacuum preloading with comparison to test data - Ze-jian Chen; Peng-lin Li; An Li; Jian-hua Yin; Ding-bao Song (Geotextiles and Geomembranes, 2024)

Rapid differential diagnosis of periprosthetic joint infection by microdroplet reaction on portable biochip and indicator - Zheng Liu; Jimei Chi; Zewei Lian; Yaqi Yang; Lijun Cheng; Xiaoxue Lin; Xuwei He; Xiaojian Ji; Chenxuan Yang; Yunhao Tang; Minzhi Yang; Zhisen Gao; et al. (Chemical Engineering Journal, 2024)

Interdecadal variability of winter and spring Eurasian snow depth and its impact on Eastern China precipitation - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Yumeng Liu; Hanhui Zhu (Climate Dynamics, 2024)
Empirical orthogonal function (EOF) and correlation analyses were employed to investigate the winter and spring snow depth in Eurasia and its relationship with Eastern China precipitation based on the observed and reanalyzed data from 1980 to 2016. The results show that the winter and spring snow cover in Eurasia not only highlights a decreasing trend due to global warming (the first EOF mode, its variance accounted for 24.4% and 22.6% of the total variance) but also exhibits notable interdecadal variation (the second EOF mode, its variance accounted for 10.2% and 11.5% of the total variance). The second EOF mode of winter snow depth in Eurasia is characterized by a west-east dipole pattern. It was observed that the spatial correlation pattern between the EOF2 of Eurasian snow depth and summer precipitation in China closely resembles the meridional quadrupole structure of the third EOF mode of summer precipitation in China. This pattern is characterized by excessive rainfall in Northeast China and the lower-middle reaches of the Yangtze River, and less rainfall over the Yellow River basin and southern China. The EOF mode of spring snow depth not only reflects the declining trend but also regulates precipitation in Eastern China. The possible mechanisms by which snow depth causes changes in soil moisture and subsequently affects atmospheric circulation are then explored from the perspective of the hydrological effects of snow cover. Decreased (Increased) snow depth in Eurasia during the winter and spring directly leads to diminished (increased) soil moisture while increasing (decreasing) net radiation and sensible heat flux at the surface. The meridional distribution of surface temperature also exhibits a dipole pattern, leading to enhanced subtropical westerly jet in the upper troposphere. The Eurasian snow cover anomalies pattern triggered an anomalous mid-latitude Eurasian wave train, which strengthened significantly in the Western Siberian Plain. It then splits into two branches, one continuing to propagate eastward at high latitudes and the other shifting towards East Asia, thereby impacting precipitation in Eastern China. This work indicates that the second EOF mode of Eurasian snow cover can impact the precipitation variability in Eastern China during the same period and in summer on an interdecadal scale.

Smoke diffusion mechanism and mitigation design for fire accidents in a tunnel-groove structure of a large hydropower station - Ruinan An; Peng Lin; Chang Liu; Maohua Zhong; Zichang Li; Wenfu Chen; Yong Xia (Tunnelling and Underground Space Technology, 2024)

Intelligent chemical profiling of 73 edible flowers by liquid chromatography-high resolution mass spectrometry combined with HRMS database and their authentication based on large-scale fingerprints - Ziqing Li; Jianqing Zhang; Lin Yang; Xiaolan Li; Qian Meng; Yun Li; Shuai Yao; Wenlong Wei; Qirui Bi; Hua Qu; Yaling An; De-an Guo (Food Chemistry, 2024)

Long-term species-level observations indicate the critical role of soil moisture in regulating China's grassland productivity relative to phenological and climatic factors - Shuai An; Xiaoqiu Chen; Fangjun Li; Xuhui Wang; Miaogen Shen; Xiangzhong Luo; Shilong Ren; Hongfang Zhao; Yan Li; Lin Xu (Science of The Total Environment, 2024)

Losing Tidal Flats at the Midpoint of the East Asian-Australasian Flyway over the past 100 Years - Wan-Jyun Chen; An-Yu Chang; Chia-Chi Lin; Ruey-Shing Lin; Da-Li Lin; Pei-Fen Lee (Wetlands, 2024)
The ecosystem services and functions of tidal flats have been overlooked for many decades, and tidal flat loss has been identified as a serious threat to many taxa in recent years, especially for migratory waterbirds. Despite the understanding of tidal flats change on the global scale, there are still a lot of unknowns on the small scale, including tidal flats in Taiwan, which are important stopover sites for migratory waterbirds along the East Asian–Australasian Flyway. Therefore, we collated historic topographic maps, Landsat Archive images between the 1920s and the 2020s to determine the trajectories of tidal flat change along the coastline of Taiwan. Our results show that tidal flat coverage expanded between the 1920s and the 1950s, but lost approximately 266 km 2 (58%) between the 1950s and the 2010s. The status of the tidal flats along the western coastline of Taiwan has been identified as “Endangered” based on the criteria of the IUCN Red List of Ecosystems. According to the aims of the Global Biodiversity Framework, we suggest rethinking the land use plans along the coastline to mitigate the tidal flat loss, especially the controversial issues concerning the expansion of green energy infrastructure. To realize the Nature Positive goals by 2030, recovering and restoring the tidal flat ecosystem could be one of the key strategies.

Direct aqueous photochemistry of methylglyoxal and its effect on sulfate formation - Jie Tan; Lingdong Kong; Yuwen Wang; Beibei Liu; Yixuan An; Lianghai Xia; Yu Lu; Qing Li; Lin Wang (Science of The Total Environment, 2024)

Sustained oxidation of Tea-Fe(III)/H2O2 simultaneously achieves sludge reduction and carbamazepine removal: The crucial role of EPS regulation - Wei Lin; Renglu Chen; Chuangxin Gong; Peter Desmond; Xu He; Jun Nan; Guibai Li; Jun Ma; An Ding; Huu Hao Ngo (Journal of Hazardous Materials, 2024)

Experimental study on metal removal characteristics of Zhundong coal to produce ultra-clean coal using acid-alkali method - Yuanmao Chen; Chang'an Wang; Yang Li; Maoyun Luo; Chenglong Yang; Lin Zhao; Zhefan Wang; Ning Fu; Defu Che (Fuel, 2024)

Synthesis and characterization of a host–guest complex based on acetylated-β-cyclodextrin and its application in improving the viscosity of supercritical carbon dioxide - Wei-An Huang; Rui Su; Jing-Wen Wang; Yu Fan; Lin Jiang; Xuan Li; Jie Cao (Fuel, 2024)

Preferentially in-situ generated copper nanograins boosting fast kinetic conversion magnesium storage of bimetallic copper-cobalt sulfide cathode - Yaping Xia; Chunxiao Chen; Lin Ran; Hou-an Zhang; Shuai Cui; Panfei Xiao; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2024)

Gelsenicine disrupted the intestinal barrier of Caenorhabditis elegans - Zekai Wu; Jian Zhang; Yajiao Wu; Mengting Chen; Hong Hu; Xinyue Gao; Chutao Li; Maodong Li; Youbo Zhang; Xiaohuang Lin; Qiaomei Yang; Li Chen; et al. (Chemico-Biological Interactions, 2024)

Impacts of physical parameterization scheme of snow and soil properties over the Tibetan Plateau on the simulation of summer rainfall in China - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Chan Wang; Hao Chen; Lunyu Shang; Shaoying Wang; Shiwen Wang; Yumeng Liu (Climate Dynamics, 2024)
Accurate representation of soil and snow state variables in the land surface model is crucial for good simulation results. In order to investigate the potential impacts of the overestimated snow cover over the Tibetan Plateau (TP) on precipitation over China, we designed comparative experiments over TP with and without updated soil texture data, soil hydrological parameters, and the fresh snow density scheme to address this issue with the Weather Research and Forecasting Model (WRF). The results show that snow cover fraction (SCF) and surface albedo in winter on the TP were overestimated in the WRF control experiment (CTL), with albedo bias exceeding 0.4 in the western TP. The SCF in the WRF improved experiment (WRFIM) is about 8% lower than that of the CTL, and the bias is decreased to 0.2–0.3 in the interior of the TP. The thermal and dynamic effects of the TP in winter have a significant impact on the weather and climate of East Asia during summer. Thus, the simulated summer rainfall bias is significantly reduced by WRFIM in North China, and the mid-lower reaches of the Yangtze River, along with the spatial correlation coefficient between the observed-based and WRF-simulated rainfall increased from 0.76 in CTL to 0.88 in WRFIM. The WRFIM-simulated reductions in snow cover and albedo cause a decrease in upward shortwave radiation and eventually increase net surface radiation. The horizontal temperature gradient of the atmosphere is increased in the WRFIM compared to the CTL, and the increased temperature in the lower and middle layers accommodates more water vapor, which is not conducive to precipitation formation. Correspondingly, the Western Pacific Subtropical High at 500 hPa in the middle troposphere weakened. The low-level anticyclonic circulation at 850 hPa also weakened to the east, affecting water vapor transport in eastern China. It leads to a decrease in the water vapor transported northward by southeasterly from the western Pacific Ocean and a decrease in the water vapor flux reaching North China. This work indicates that accurate characterization of soil properties and snow cover on the TP is crucial for improving the simulation bias of summer rainfall in China.

PI3K/AKT mediated De novo fatty acid synthesis regulates RIG-1/MDA-5-dependent type I IFN responses in BVDV-infected CD8+T cells - Shan-shan Liu; Tong-tong Bai; Tao-lin Que; An Luo; Yu-xin Liang; Yu-xin Song; Tian-yi Liu; Jin-wei Chen; Jing Li; Nan Li; Ze-chen Zhang; Nan-nan Chen; et al. (Veterinary Microbiology, 2024)

Efficacy and mechanism of copper removal from electroplating wastewater by schwertmannite-like mineral - Ni Li; Mingyan Shi; Yimiao Lan; Hongguo Zhang; Guanfeng An; Shaonan Lin; Langming Xue (Journal of Environmental Chemical Engineering, 2024)

Atmospheric VOCs in an industrial coking facility and the surrounding area: Characteristics, spatial distribution and source apportionment - Meicheng Wen; Weiqiang Deng; Jin Huang; Shu Zhang; Qinhao Lin; Chao Wang; Shengtao Ma; Wanjun Wang; Xin Zhang; Guiying Li; Taicheng An (Journal of Environmental Sciences, 2024)

PCSK9 regulates myocardial ischemia–reperfusion injury through parkin/pink1-mediated autophagy pathway - Guangwei Huang; Hailong Bao; Peng Zhan; Xiyang Lu; Zonggang Duan; Xinlin Xiong; Muzhi Lin; Bing Wang; Hongxin An; Luanda Xiahou; Haiyan Zhou; Zhenhua Luo; et al. (Molecular & Cellular Toxicology, 2024)

Synergistic Effects of Bay of Bengal Tropical Cyclones and Tibetan Plateau Vortices on Water Vapor Transport over the Tibetan Plateau in Early Summer - Jialu Lin; Ying Li; Beiyao Liu; Pengchao An (Journal of Meteorological Research, 2024)

Associations of residential greenness exposure and ambient air pollutants with newly-diagnosed drug-resistant tuberculosis cases - Wan-mei Song; Yi Liu; Dan Men; Shi-jin Li; Ning-ning Tao; Qian-yun Zhang; Si-qi Liu; Qi-qi An; Xue-han Zhu; Qi-lin Han; Yu-zhen Zhang; Ying-ying Li; et al. (Environmental Science and Pollution Research, 2024)

Review: The application of source analysis methods in tracing urban non-point source pollution: categorization, hotspots, and future prospects - Bingquan Lin; Fei Qi; Xinqi An; Chen Zhao; Yahong Gao; Yuxuan Liu; Yin Zhong; Bin Qiu; Zhenbei Wang; Qian Hu; Chen Li; Dezhi Sun (Environmental Science and Pollution Research, 2024)

Active dark carbon fixation evidenced by 14C isotope assimilation and metagenomic data across the estuarine-coastal continuum - Bolin Liu; Yanling Zheng; Xinyu Wang; Lin Qi; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Science of The Total Environment, 2024)

Natural product-derived ferroptosis mediators - Yi-Li Chen; Lin-An Xiong; Lie-Feng Ma; Luo Fang; Zha-Jun Zhan (Phytochemistry, 2024)

Visible light-driven Cl-g-C3N4 activated peroxydisulfate process for TMP efficient degradation in a wide pH range - Jie Chen; Jiashuai Hu; Yuanmao Lin; Xiaoling Liu; Jie Liang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Xiaochan An; Xiaobing Chen; Xiaojun Chen; et al. (Journal of Water Process Engineering, 2024)

Effect of EDDS on the rhizosphere ecology and microbial regulation of the Cd-Cr contaminated soil remediation using king grass combined with Piriformospora indica - Haixiang Zhang; Kailu Zhang; Yali Duan; Xiaoyan Sun; Li Lin; Qianli An; Muhammad Mohsin Altaf; Zhiqiang Zhu; Fan Liu; Yangqiu Jiao; Jing Yin; Can Xie; et al. (Journal of Hazardous Materials, 2024)

Natural deep eutectic solvent: A promising eco-friendly food bio-inspired antifreezing - Xue Li; Jia-Ying Li; Muhammad Faisal Manzoor; Qiu-Ya Lin; Jia-ling Shen; Lan Liao; Xin-An Zeng (Food Chemistry, 2024)

Risk assessment of pesticide compounds: IPT and TCZ cause hepatotoxicity, activate stress pathway and affect the composition of intestinal flora in red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wei-Ren Dong; Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Guang-Xu Liu; Miao-An Shu (Environmental Pollution, 2024)

Cathepsin B degrades RbcL during freezing-induced programmed cell death in Arabidopsis - Gang Yang; Tao Chen; Ting-ting Fan; Xiang-yu Lin; Yu-qiong Cui; Wei-chao Dong; Li-zhe An; Hua Zhang (Plant Cell Reports, 2024)

Effects of an intraoperative intravenous Bolus Dose of Dexmedetomidine on postoperative catheter-related bladder discomfort in male patients undergoing transurethral resection of bladder tumors: a randomized, double-blind, controlled trial - Tianhua Zhang; Huiting Li; Chunnan Lin; Rui An; Wenqian Lin; Hongying Tan; Longhui Cao (European Journal of Clinical Pharmacology, 2024)

Physiology, microcystin production, and transcriptomic responses of Microcystis aeruginosa exposed to calcium and magnesium - Li Yin; Lin Xu; Kaipian Shi; Weiyu Chen; Yong Zhang; Juan Wang; Junfeng An; Huan He; Shaogui Yang; Lixiao Ni; Shiyin Li (Science of The Total Environment, 2024)

Multi-source exposure and health risks of phthalates among university students in Northeastern China - Huicheng Zhu; Na Zheng; Changcheng Chen; Ning Li; Qirui An; Wenhui Zhang; Qiuyan Lin; Zhifei Xiu; Siyu Sun; Xiaoqian Li; Yunyang Li; Sujing Wang (Science of The Total Environment, 2024)

Structural and functional analysis of transforming growth factor beta regulator 1 (TBRG1) in the red swamp crayfish Procambarus clarkii: The initial insight into TBRG1's role in invertebrate immunity - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2024)

Association of urinary polycyclic aromatic hydrocarbon metabolites with gestational diabetes mellitus and gestational hypertension among pregnant women in Southwest China: A cross-sectional study - Dengqing Liao; Shimin Xiong; Songlin An; Lin Tao; Lulu Dai; Yingkuan Tian; Wei Chen; Caidie He; Pei Xu; Nian Wu; Xiang Liu; Haonan Zhang; et al. (Environmental Pollution, 2024)

Investigation of ammonia-induced lethal toxicity toward ion regulation in zebrafish embryos - Li-Yih Lin; Chieh-An Cheng; Sian-Tai Liu; Jiun-Lin Horng (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2024)

An asymmetric electrode matching reversible kinetics of oxygen reaction for a rechargeable Zn-air battery - Shuxin Li; Han Zhang; Lin Wu; Hongwei Zhao; Lin Tao; Lixiang Li; Chengguo Sun; Dongying Ju; Baigang An (Chemical Engineering Journal, 2024)

Application of an absolute reference frame for methane clumped-isotope analyses - Qingmei Liu; Jiacheng Li; Wenmin Jiang; Yun Li; Mang Lin; Wen Liu; Yanhua Shuai; Haizu Zhang; Ping'an Peng; Yongqiang Xiong (Chemical Geology, 2024)

Groundwater Quality and Vulnerability Assessment in a Semiarid Karst Region of Northern China - Ran An; Shu Wang; Zongjun Gao; Zhenyan Wang; Wei Li; Qijun Deng; Lü Lin; Yuanqing Liu (Journal of Earth Science, 2024)

In situ biomass burning enhanced the contribution of biogenic sources to sulfate aerosol in subtropical cities - Tingting Li; Jun Li; Luhua Xie; Boji Lin; Hongxing Jiang; Rong Sun; Xiao Wang; Ben Liu; Chongguo Tian; Qilu Li; Wanglu Jia; Gan Zhang; et al. (Science of The Total Environment, 2024)

Bibliometric analysis and systematic review of the adherence, uptake, translocation, and reduction of micro/nanoplastics in terrestrial plants - Yang Li; Lin Zhao; Yi An; Li Qin; Zhi Qiao; Daying Chen; Yihan Li; Hongzhi Geng; Yongkui Yang (Science of The Total Environment, 2024)

Diverse Late Triassic arc magmatism and porphyry Cu deposits in the southeastern Tibetan Plateau: Related to slab tear along a subducting passive margin? - Wan-Li Tang; Jian-Lin Chen; Tian-Nan Yang; An Yin; Ji-Feng Xu; Jiang-Bo Ren (Lithos, 2024)

Piriformospora indica colonization enhances remediation of cadmium and chromium co-contaminated soils by king grass through plant growth promotion and rhizosphere microecological regulation - Kailu Zhang; Haixiang Zhang; Can Xie; Zhiqiang Zhu; Li Lin; Qianli An; Xin Zhang; Weidong Wu; Dong Li (Journal of Hazardous Materials, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Anthropogenically-induced atmospheric Pb cycle in low-latitude Asia since the Industrial Revolution recorded by high-resolution stalagmites - Tianli Wang; Pei-Hsuan Yao; Chuan-Chou Shen; Sakonvan Chawchai; Adi Torfstein; Ashish Sinha; Hai Xu; Tsai-Luen Yu; Fangyuan Lin; Xiqian Wang; Dong Li; Hai Cheng; et al. (Global and Planetary Change, 2024)

Regional complex system simulation optimization through linking governance and environment performance: A case study of water environmental carrying capacity based on the SDES model - An Huang; Li Tian; Yongfu Li; Binyu Xiong; Jianghao Yu; Yuan Gao; Qing Li; Chenjing Fan; Linxiner Liu; Xuejun Duan; Chen Lin (Environmental Impact Assessment Review, 2024)

Emerging and legacy perfluoroalkyl and polyfluoroalkyl substances (PFAS) in surface water around three international airports in China - Jing Liu; Zhen Zhao; Jie Li; Xia Hua; Boxuan Zhang; Caijun Tang; Xinyi An; Tian Lin (Chemosphere, 2023)

Energy effective utilization of circulating fluidized bed fly ash to prepare silicon-aluminum composite aerogel and gypsum - Jia-Yong Li; Bao-Hua Tian; Xin-Xin Li; Zhe Wang; Li-Ping Cui; Dan-Dan Liang; Shuang-Lin Wang; Yu-He Liu; Heng-An Ou; Hai-Xia Liang (Waste Management, 2023)

Long-lived Cenozoic positive relief of the south-Eastern Tian Shan: Insights from provenance analyses of the northwestern Kuqa Depression sediments - Jialun Huang; Xiubin Lin; Kaixuan An; Hanlin Chen; Xiaogan Cheng; Yang Qu; Yong Li; Xianzhang Yang; Liang Zhang; Cai Chen; Zhuxin Chen; Lin Jiang; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Yuexiconcha nov. gen. – A resilifer-bearing palaeotaxodont (Bivalvia, Protobranchia) from the Ordovician of Guangdong, South China - Zhi-jun Niu; Ren-jie Zhang; Paul A. Johnston; Chu-an Li; Zhi-hong Wang; Kun Hu; Fang Song; Yao-yan He; Jin-lan He; Xiao-ming Lin; Wen-qiang Yang (Geobios, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

In-situ generated elemental selenium nanograins cooperated with NiSe2 microspheres for significantly enhanced magnesium-storage performance - Changchun Hu; Lin Ran; Hou-an Zhang; Shuai Cui; Fei Xu; Daohong Zhang; Ting Li (Chemical Engineering Journal, 2023)

Iodine status and associated dietary factors among preschool children in Shanghai - Jing Li; Jun-Xia Liu; Yu-Qing Wang; An-Xin Lu; Yi-Hong Wang; Yin Lin; Chong-Huai Yan (Environmental Science and Pollution Research, 2023)

Tidal dynamics regulates potential coupling of carbon‑nitrogen‑sulfur cycling microbes in intertidal flats - Yuhui Niu; Zhirui An; Dengzhou Gao; Feiyang Chen; Jie Zhou; Bolin Liu; Lin Qi; Li Wu; Zhuke Lin; Guoyu Yin; Xia Liang; Hongpo Dong; et al. (Science of The Total Environment, 2023)

Characteristics of landscape and erosion in the Eastern Pamir and their implications for regional fault connections - Yunpeng Wu; Rong Yang; Junqing He; Hanlin Chen; Xiubin Lin; Xuhua Shi; Kaixuan An; Chunyang Li; Shibao Gao; Yaguang Chen (Geomorphology, 2023)

A novel integrated automatic strategy for amino acid composition analysis of seeds from 67 species - Yelin Ding; Qirui Bi; Dongdong Huang; Jingmei Liao; Lin Yang; Xiaoxiao Luo; Peilei Yang; Yun Li; Changliang Yao; Wenlong Wei; Jianqing Zhang; Jiayuan Li; et al. (Food Chemistry, 2023)

Effects of food-borne docosahexaenoic acid supplementation on bone lead mobilisation, mitochondrial function and serum metabolomics in pre-pregnancy lead-exposed lactating rats - An-Xin Lu; Yin Lin; Jing Li; Jun-Xia Liu; Chong-Huai Yan; Lin Zhang (Environmental Pollution, 2023)

Metabolomics insights into the effects of pre-pregnancy lead exposure on bone metabolism in pregnant rats - Lin Zhang; Yin Lin; An-Xin Lu; Jun-Xia Liu; Jing Li; Chong-Huai Yan (Environmental Pollution, 2023)

Super-strong Zn and S atomic terminals in an organic/inorganic hybrid S-scheme polyimide based heterojunction for efficient photocatalytic treatment of mixed pollutant wastewater - Siyi Li; Yushu Wang; Hongli An; Junjun Lin; Shuang Jiang; Tianyong Zhang; Bin Li (Chemical Engineering Journal, 2023)

In-situ utilization of EPS improves the directional oxidation ability of Fe(III)/H2O2 and enhances sludge dewaterability - Wei Lin; Chuangxin Gong; Renglu Chen; Xu He; Jun Nan; Guibai Li; Huu Hao Ngo; An Ding (Chemical Engineering Journal, 2023)

Movement of protistan trophic groups in soil–plant continuums - Chenshuo Lin; Wen‐Jing Li; Li‐Juan Li; Roy Neilson; Xin‐Li An; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Protists, functionally divided into consumers, phototrophs, and parasites act as integral components and vital regulators of microbiomes in soil–plant continuums. However, the drivers of community structure, assembly mechanisms, co‐occurrence patterns, and the associations with human pathogens and different protistan trophic groups remain unknown. Here, we characterized the phyllosphere and soil protistan communities associated with three vegetables under different fertilization treatments (none and organic fertilization) at five growth stages. In this study, consumers were the most diverse soil protist group, had the role of inter‐kingdom connector, and were the primary biomarker for rhizosphere soils which were subjected to decreasing deterministic processes during plant growth. In contrast, phototrophs had the greatest niche breadth and formed soil protistan hubs, and were the primary biomarkers for both bulk soils and the phyllosphere. Parasites had minimal input to microbial co‐occurrence networks. Organic fertilization increased the relative abundance (RA) of pathogenic protists and the number of pathogen–consumer connections in rhizosphere soils but decreased protistan richness and the number of internal protistan links. This study advances our understanding of the ecological roles and potential links between human pathogens and protistan trophic groups associated with soil–plant continuums, which is fundamental to the regulation of soil–plant microbiomes and maintenance of environmental and human health.

Monitoring and management of abandoned, lost and discarded fishing gear (ALDFG) in Penghu Islands, Taiwan - Wen-Hong Liu; Hung-An Chang; Hao-Tang Jhan; Chih-Cheng Lin; Li-Shu Chen; Chung-Lun Liu; Kuo-Huan Ting (Marine Pollution Bulletin, 2023)

An MLS-based high-accuracy measurement and automatic analysis method for roadway deformation - Chao Wu; Yuanhui Li; Long An; Erhu Dong; Lin Han (Tunnelling and Underground Space Technology, 2023)

A comprehensive analysis of the Bencao (herbal) small RNA Atlas reveals novel RNA therapeutics for treating human diseases - Yinghao Cao; Yexuan Lin; Na Sun; Xinyi Du; Yixin Dong; Song Mei; Xingyu Deng; Xiaobei Li; Shaoting Guo; Kegong Tang; Jiaqi Liu; Xiangyu Qiao; et al. (Science China Life Sciences, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Selenium alleviates biological toxicity of thiamethoxam (TMX): Bioaccumulation of TMX, organ damage, and antioxidant response of red swamp crayfish (Procambarus clarkii) - Yan-Mei Zhang; Wen-Bin Xu; Chen-Yang Lin; Bang-Ze Li; Miao-An Shu (Journal of Hazardous Materials, 2023)

Identification and functional analysis of cytosolic phospholipase A2 (cPLA2) from the red swamp crayfish Procambarus clarkii: The first evidence of cPLA2 involved in immunity in invertebrates - Chen-Yang Lin; Wen-Bin Xu; Bang-Ze Li; Miao-An Shu; Yan-Mei Zhang (Fish & Shellfish Immunology, 2023)

Internal exposure risk based on urinary metabolites of PAHs of occupation and non-occupation populations around a non-ferrous metal smelting plant - Bizhi Wu; Meiqing Lin; Hailing Li; Yingjun Wu; Mengdie Qi; Jian Tang; Shengtao Ma; Guiying Li; Taicheng An (Journal of Hazardous Materials, 2023)

Star-like, dopant-free, corannulene-cored hole transporting materials for efficient inverted perovskite solar cells - Ming-Wei An; Bolin Li; Bin-Wen Chen; Zuo-Chang Chen; Han-Rui Tian; Lin-Long Deng; Xugang Guo; Zhou Xing (Chemical Engineering Journal, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Effect of using construction and demolition waste as substrate on methane and carbon dioxide emissions from green roofs - Xinping Li; Yuanmao Lin; Xiaoling Liu; Jie Liang; Xin Yang; Ke Zhang; Bing Jiang; Hongbing Luo; Lin Li; Zhaolan Wei; Xiaochan An; Wei Chen; et al. (Ecological Engineering, 2023)

Ethanol production using the whole solid-state fermented sugarcane bagasse cultivated by Trichoderma reesei RUT-C30 supplemented with commercial cellulase - Ching An Lin; Cheng Cheng; Li Wei Chen; C. Will Chen; Kow Jen Duan (Biocatalysis and Agricultural Biotechnology, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

SHP2: its association and roles in systemic lupus erythematosus - Chan Yang; Rong Li; Lin-Chong Su; You-Yu Lan; You-Qiang Wang; Wang-Dong Xu; An-Fang Huang (Inflammation Research, 2023)

Potential response of dark carbon fixation to global warming in estuarine and coastal waters - Lin Qi; Yanling Zheng; Lijun Hou; Bolin Liu; Jie Zhou; Zhirui An; Li Wu; Feiyang Chen; Zhuke Lin; Guoyu Yin; Hongpo Dong; Xiaofei Li; et al. (Global Change Biology, 2023)
Dark carbon fixation (DCF), through which chemoautotrophs convert inorganic carbon to organic carbon, is recognized as a vital process of global carbon biogeochemical cycle. However, little is known about the response of DCF processes in estuarine and coastal waters to global warming. Using radiocarbon labelling method, the effects of temperature on the activity of chemoautotrophs were investigated in benthic water of the Yangtze estuarine and coastal areas. A dome‐shaped thermal response pattern was observed for DCF rates (i.e., reduced rates at lower or higher temperatures), with the optimum temperature ( T opt ) varying from about 21.9 to 32.0°C. Offshore sites showed lower T opt values and were more vulnerable to global warming compared with nearshore sites. Based on temperature seasonality of the study area, it was estimated that warming would accelerate DCF rate in winter and spring but inhibit DCF activity in summer and fall. However, at an annual scale, warming showed an overall promoting effect on DCF rates. Metagenomic analysis revealed that the dominant chemoautotrophic carbon fixation pathways in the nearshore area were Calvin‐Benson‐Bassham (CBB) cycle, while the offshore sites were co‐dominated by CBB and 3‐hydroxypropionate/4‐hydroxybutyrate cycles, which may explain the differential temperature response of DCF along the estuarine and coastal gradients. Our findings highlight the importance of incorporating DCF thermal response into biogeochemical models to accurately estimate the carbon sink potential of estuarine and coastal ecosystems in the context of global warming.

Association between nitrogen dioxide concentration and hypertension hospitalization: A multicenter time-series analysis in Xinxiang, China - Shi-qi Ge; Yong-bin Wang; Fei Lin; Run-ran Miao; Kai Zhang; Li Li; Hui-ge Guo; Qian Wang; Li Zhang; Zhi-gang Chen; Guo-an Zhao (Atmospheric Pollution Research, 2023)

Dataset of Comparative Observations for Land Surface Processes over the Semi-Arid Alpine Grassland against Alpine Lakes in the Source Region of the Yellow River - Xianhong Meng; Shihua Lyu; Zhaoguo Li; Yinhuan Ao; Lijuan Wen; Lunyu Shang; Shaoying Wang; Mingshan Deng; Shaobo Zhang; Lin Zhao; Hao Chen; Di Ma; et al. (Advances in Atmospheric Sciences, 2023)
Thousands of lakes on the Tibetan Plateau (TP) play a critical role in the regional water cycle, weather, and climate. In recent years, the areas of TP lakes underwent drastic changes and have become a research hotspot. However, the characteristics of the lake-atmosphere interaction over the high-altitude lakes are still unclear, which inhibits model development and the accurate simulation of lake climate effects. The source region of the Yellow River (SRYR) has the largest outflow lake and freshwater lake on the TP and is one of the most densely distributed lakes on the TP. Since 2011, three observation sites have been set up in the Ngoring Lake basin in the SRYR to monitor the lake-atmosphere interaction and the differences among water-heat exchanges over the land and lake surfaces. This study presents an eight-year (2012–19), half-hourly, observation-based dataset related to lake–atmosphere interactions composed of three sites. The three sites represent the lake surface, the lakeside, and the land. The observations contain the basic meteorological elements, surface radiation, eddy covariance system, soil temperature, and moisture (for land). Information related to the sites and instruments, the continuity and completeness of data, and the differences among the observational results at different sites are described in this study. These data have been used in the previous study to reveal a few energy and water exchange characteristics of TP lakes and to validate and improve the lake and land surface model. The dataset is available at National Cryosphere Desert Data Center and Science Data Bank.

Polybrominated diphenyl ethers and bromophenols in paired serum, hair, and urine samples of e-waste dismantlers: Insights into hair as an indicator of endogenous exposure - Meiqing Lin; Shengtao Ma; Jian Tang; Yingxin Yu; Guiying Li; Ruifang Fan; Guoxia Zhang; Bixian Mai; Taicheng An (Science of The Total Environment, 2023)

Failure mechanism of a large-scale composite deposits caused by the water level increases - Xin Zhang; Guo-xiang Tu; Qi-feng Luo; Hao Tang; Yu-lin Zhang; An-run Li (Journal of Mountain Science, 2023)

In vitro and in vivo anti-tumor activity of Coenzyme Q0 against TWIST1-overexpressing HNSCC cells: ROS-mediated inhibition of EMT/metastasis and autophagy/apoptosis induction - Hsin-Ling Yang; Li-Wen Chiu; Yi-An Lin; Sudhir Pandey; Chithravel Vadivalagan; Jiunn-Wang Liao; Yugandhar Vudhya Gowrisankar; Hui-Jye Chen; Hui-Yi Lin; You-Cheng Hseu (Toxicology and Applied Pharmacology, 2023)

The ginsenoside Rh2 protects porcine oocytes against aging and oxidative stress by regulating SIRT1 expression and mitochondrial activity - Hongye Liu; Zhi-Yong An; Zhou-Yan Li; Liu-Hui Yang; Xiu-Li Zhang; Yan-Tong Lv; Xi-Jun Yin; Lin-Hu Quan; Jin-Dan Kang (Theriogenology, 2023)

Effects of low salinity stress on osmoregulation and gill transcriptome in different populations of mud crab Scylla paramamosain - Wen-Bin Xu; Yan-Mei Zhang; Bang-Ze Li; Chen-Yang Lin; Da-Yong Chen; Yuan-Xin Cheng; Xiao-Ling Guo; Wei-Ren Dong; Miao-An Shu (Science of The Total Environment, 2023)

Toward sustainable inland aquaculture: Coastal subsidence monitoring in Taiwan - Wei-Chia Hung; Cheinway Hwang; Luigi Tosi; Shao-Hung Lin; Pei-Ching Tsai; Yi-An Chen; Wei-Ji Wang; En-Cheng Li; Sihao Ge (Remote Sensing Applications: Society and Environment, 2023)

The content and distribution of 18 phenolic compounds in 462 batches of edible flowers from 73 species commercially available in China - Ziqing Li; Jianqing Zhang; Qian Meng; Lin Yang; Mingyang Qiu; Yun Li; Shuai Yao; Wenlong Wei; Changliang Yao; Qirui Bi; Jiayuan Li; De-an Guo (Food Research International, 2023)

Isolation, identification and the pathogenicity characterization of a Santee-Cooper ranavirus and its activation on immune responses in juvenile largemouth bass (Micropterus salmoides) - Xiaodan Liu; Yanbing Zhang; Zheling Zhang; Zhenhua An; Xiaojun Zhang; Vikram N. Vakharia; Li Lin (Fish & Shellfish Immunology, 2023)

Recent progress on highly efficient removal of heavy metals by layered double hydroxides - Tong He; Qian Li; Tong Lin; Jiaxin Li; Sha Bai; Sai An; Xianggui Kong; Yu-Fei Song (Chemical Engineering Journal, 2023)

An Investigation of Bubble Motion in the Fluidic Oscillator - Haiyan Bie; Licheng Xue; Yulong Li; Yunxia Li; Zixin Lin; Weizhong An (Journal of Ocean University of China, 2023)

Human umbilical cord mesenchymal stem cell-derived exosomes carrying miR-1827 downregulate SUCNR1 to inhibit macrophage M2 polarization and prevent colorectal liver metastasis - Jierong Chen; Ziyue Li; Caifeng Yue; Jianhong Ma; Lixue Cao; Jiaxin Lin; Dandan Zhu; Ran An; Jinxin Lai; Yunmiao Guo; Bing Gu (Apoptosis, 2023)

Integrated optimization of real-time order acceptance and flexible job-shop rescheduling with multi-level imperfect maintenance constraints - Youjun An; Xiaohui Chen; Kaizhou Gao; Lin Zhang; Yinghe Li; Ziye Zhao (Swarm and Evolutionary Computation, 2023)

Do tillage systems affect the cadmium threshold in farmland soil for environmental quality standard setting? - Zhaolin Du; Weiqiang Dou; Dasong Lin; Li Qin; Yi An; Hongan Chen; Lina Wu; Liyan Mou (Science of The Total Environment, 2023)

Risk assessment and environmental determinants of urinary phthalate metabolites in pregnant women in Southwest China - Nian Wu; Lin Tao; Kunming Tian; Xia Wang; Caidie He; Songlin An; Yingkuan Tian; Xiang Liu; Wei Chen; Haonan Zhang; Pei Xu; Dengqing Liao; et al. (Environmental Science and Pollution Research, 2023)

Effects of periodic drying-wetting on microbial dynamics and activity of nitrite/nitrate-dependent anaerobic methane oxidizers in intertidal wetland sediments - Feiyang Chen; Yuhui Niu; Zhirui An; Li Wu; Jie Zhou; Lin Qi; Guoyu Yin; Hongpo Dong; Xiaofei Li; Dengzhou Gao; Min Liu; Yanling Zheng; et al. (Water Research, 2023)

Enhanced sludge dewaterability by ferrate/ferric chloride: The key role of Fe(IV) on the changes of EPS properties - Wei Lin; Junmin Guo; Jie Zeng; Renglu Chen; Huu Hao Ngo; Jun Nan; Guibai Li; Jun Ma; An Ding (Science of The Total Environment, 2023)

Transcriptomic data recover a new superfamily-level phylogeny of Cucujiformia (Coleoptera, Polyphaga) - Ming-Long Yuan; Wen-Ting Chen; Qi-Lin Zhang; Min Li; Li Zhang; Pei-An Tang (Molecular Phylogenetics and Evolution, 2023)

Characterization of fibroblast growth factor receptor 4 (FGFR4) from the red swamp crayfish Procambarus clarkii and its role in antiviral and antimicrobial immune responses - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wen-Bin Xu; Wei-Ren Dong; Miao-An Shu (Journal of Invertebrate Pathology, 2023)

Handwipes as indicators to assess organophosphate flame retardants exposure and thyroid hormone effects in e-waste dismantlers - Jian Tang; Shengtao Ma; Xin Hu; Meiqing Lin; Guiying Li; Yingxin Yu; Taicheng An (Journal of Hazardous Materials, 2023)

Comprehensive application possibility: Construction hydrophilic, amphiphilic and hydrophobic system of modified zein by enzymatic or cysteine modification - An-Qi Zhang; Xiao-Yan Li; Bo-Hao Liu; Yu-Qi Yin; Han-Lin Zhang; Ying-Hua Zhang (Food Hydrocolloids, 2023)

The toxicity of nano polyethylene terephthalate to mice: Intestinal obstruction, growth retardant, gut microbiota dysbiosis and lipid metabolism disorders - Xiaoying Lin; Hongxin Xie; Yanfei Zhang; Xue Tian; Liwei Cui; Nianqiu Shi; Liming Wang; Jiating Zhao; Lihui An; Jing Wang; Bai Li; Yu-Feng Li (Food and Chemical Toxicology, 2023)

Effects of secondary impinging on flow features and mixing performance in T-T jet reactors - Haiyan Bie; Licheng Xue; Yue Wang; Zongrui Hao; Gang Liu; Yunxia Li; Zixin Lin; Weizhong An (Chemical Engineering Journal, 2023)

The largest rock avalanche in China at Iymek, Eastern Pamir, and its spectacular emplacement landscape - An-Wen Shi; Yu-Feng Wang; Qian-Gong Cheng; Qi-Wen Lin; Tian-Hua Li; Bernd Wünnemann (Geomorphology, 2023)

Bioaccumulation of Cd and comparative transcriptome analysis after the antagonism of Se in the hepatopancreas of estuary mud crab (Scylla paramamosain) - Yan-Mei Zhang; Chen-Yang Lin; Bang-Ze Li; Wei-Ren Dong; Miao-An Shu (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2023)

One-step fabrication of self-healing poly(thioctic acid) coatings on ZE21B Mg alloys for enhancing corrosion resistance, anti-bacterial/oxidation, hemocompatibility and promoting re-endothelialization - Zhao-Qi Zhang; Pei-Duo Tong; Li Wang; Zheng-Hui Qiu; Jing-An Li; Hang Li; Shao-Kang Guan; Cun-Guo Lin; Hong-Yan Wang (Chemical Engineering Journal, 2023)

Correlation analysis between the occurrence of epidemic in ancient China and solar activity - Si Chen; Yong Wei; Xin’an Yue; Kaihua Xu; Mingkun Li; Wei Lin (Science China Earth Sciences, 2023)

Residues of polychlorinated biphenyls (PCBs) in a wild predatory fish from an e-waste site in South China between 2009 and 2016 - Chang-an Li; Si-sheng Li; Ying Zhang; Yichao Huang; Lin Tao (Environmental Science and Pollution Research, 2023)

Acinetobacter faecalis Sp. Nov., Isolated from Elephant Faeces - Xue-Mei Chen; De-Feng An; Si-Rong He; Shao-Juan Yang; Zu-Zhen Yang; Lian-Shuang Xiong; Gui-Ding Li; Ming-Guo Jiang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2023)

Effects of exposure to phthalate during early pregnancy on gestational diabetes mellitus: a nested case–control study with propensity score matching - Wei Chen; Caidie He; Xiang Liu; Songlin An; Xia Wang; Lin Tao; Haonan Zhang; Yingkuan Tian; Nian Wu; Pei Xu; Dengqing Liao; Juan Liao; et al. (Environmental Science and Pollution Research, 2022)

Associations of exposure to lead and cadmium with risk of all-cause and cardiovascular disease mortality among patients with type 2 diabetes - Kai Zhu; Yuge Zhang; Qi Lu; Tingting Geng; Rui Li; Zhenzhen Wan; Xuena Zhang; Yujie Liu; Lin Li; Zixin Qiu; Meian He; Liegang Liu; et al. (Environmental Science and Pollution Research, 2022)

New loci for refractive errors and ocular biometric parameters in young Chinese Han adults - Yunyun Sun; Zi-Bing Jin; Shifei Wei; Hongyan Jia; Kai Cao; Jianping Hu; Caixia Lin; Wenzai An; Jiyuan Guo; He Li; Jing Fu; Shi-Ming Li; et al. (Science China Life Sciences, 2022)

The Key Role of Magnetic Resonance Imaging in the Detection of Neurodegenerative Diseases-Associated Biomarkers: A Review - Ke-Ru Li; An-Guo Wu; Yong Tang; Xiao-Peng He; Chong-Lin Yu; Jian-Ming Wu; Guang-Qiang Hu; Lu Yu (Molecular Neurobiology, 2022)

How Frequently Will the Persistent Heavy Rainfall over the Middle and Lower Yangtze River Basin in Summer 2020 Happen under Global Warming? - Zi-An Ge; Lin Chen; Tim Li; Lu Wang (Advances in Atmospheric Sciences, 2022)

Influence of asymmetric blockage of the drainage system of a deep-buried tunnel on water gushing - He-lin Fu; Peng-tao An; Yi-min Wu; Jie Li; Long Chen (Journal of Mountain Science, 2022)

Fine mapping qKRN5.04 provides a functional gene negatively regulating maize kernel row number - Yixin An; Lin Chen; Yong-Xiang Li; Chunhui Li; Yunsu Shi; Dengfeng Zhang; Yu Li; Tianyu Wang (Theoretical and Applied Genetics, 2022)

Zkscan3 affects erythroblast development by regulating the transcriptional activity of GATA1 and KLF1 in mice - Zixuan Li; Binjie Sheng; Tingting Zhang; Tian Wang; Dan Chen; Gangli An; Xingbing Wang; Huimin Meng; Lin Yang (Journal of Molecular Histology, 2022)
ZKSCAN3 encodes a zinc-finger transcription factor that regulates the expression of important genes and plays a significant role in tumor development, pathogenesis, and metastasis. However, its biological functions under normal physiological conditions remain largely unknown. In our previous studies, using flow cytometry, we found that the deletion of Zkscan3 may cause abnormal erythropoiesis. In this study, we found that, in a Zkscan3 knockout mice model, the number of splenic early-stage (basophilic-erythroblasts) and late-stage (chromatophilic-erythroblasts to polychromatophilic-erythroblasts through orthochromatophilic-erythroblasts) erythroblasts increased, whereas the number of late erythroblasts in the bone marrow decreased. Moreover, the phenotype was exacerbated after treating mice with phenylhydrazine (PHZ), which causes severe hemolytic anemia. In the knockout mice treated with PHZ, the percentage of reticulocyte in the peripheral blood conspicuously increased, whereas MCHC and red blood cells decreased. Then, we performed RNA-seq and quantitative-polymerase chain reaction assay and found that the expression of GATA1 and Tiam1 in erythroblasts were upregulated, whereas KLF1 was downregulated. Luciferase assays showed that Zkscan3 inhibited the transcription of GATA1 and Tiam1 and promoted the expression of KLF1 . Additionally, ChIP and CO-IP results confirmed that Zkscan3 directly interacts with GATA1 and inhibits its transcriptional activity in MEL cells. Our results demonstrate, for the first time, the significant role of Zkscan3 in physiological erythropoiesis through the interaction with GATA1, both at the DNA and protein level, and with Tiam1 and KLF1 at the DNA level.

The impact of Alzheimer's disease susceptibility loci on lateral ventricular surface morphology in older adults - Shan Li; Na An; Nan Chen; Yin Wang; Lin Yang; Yalin Wang; Zhijun Yao; Bin Hu (Brain Structure and Function, 2022)

Evaluation of surface albedo over the Tibetan Plateau simulated by CMIP5 models using in‐situ measurements and MODIS - Yingying An; Xianhong Meng; Lin Zhao; Zhaoguo Li; Shaoying Wang; Lunyu Shang; Hao Chen; Shihua Lyu (International Journal of Climatology, 2022)
Surface albedo plays a key role in the energy and water cycles, and reasonable parameterizations of surface albedo will be greatly helpful to improve the simulation of radiation partition in climate models. In‐situ measurements of albedo from five sites over the Tibetan Plateau (TP) and MODIS albedo product are used to evaluate monthly, annual, and seasonal variations of the surface albedo simulated by 24 Global Climate Models (GCMs) archived by the Coupled Model Intercomparison Project Phase 5 (CMIP5). Potential factors contributing to the bias of simulated albedo were investigated. The results show that the monthly albedo of 24 GCMs varied across models, and the difference among the models was smaller in the June–July–August period than the December–January–February period. The ensemble mean albedo of the 24 GCMs was more consistent with the in‐situ measurements than the individual model. The albedo calculated from the BNU‐ESM, GFDL‐CM3, INM‐CM4, MIROC4h, MIROC‐ESM, and MIROC‐ESM‐CHEM models coincided with the observations from June to September, increasing rapidly to above 0.4 from November. However, the annual cycle of surface albedo was insignificant when simulated by some models, such as CanESM2, CSIRO‐Mk3.6.0, CMCC‐CMS, IPSL‐CM5A‐MR, and MPI‐ESM‐MR. Additionally, the surface albedo was overestimated by CMIP5 multi‐model ensemble mean—with a smaller amplitude of daily albedo—compared with the values estimated from in‐situ observations and MCD43A3. In all 24 models, snow albedo parameterization schemes were found to variably fit the attenuation of snow albedo over time. The cold temperature, relatively more precipitation, fresh snow density, and albedo in these models led to large biases in snow depth and ablation. The surface albedo tends to increase without the influence of blowing snow and withered grass on the model's albedo.

Nakamurella leprariae sp. nov., isolated from a lichen sample - De-Feng An; Shao-Juan Yang; Long-Qian Jiang; Xin-Yu Wang; Xiao-Yu Huang; Lei Lang; Xue-Mei Chen; Ming-Qun Fan; Gui-Ding Li; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; et al. (Archives of Microbiology, 2022)

Species Composition and Assemblages of Ichthyoplankton in Sansha Bay, Fujian Province, China - Yan Jiang; Bai-an Lin; Hao-yang He; Guang-mao Ding; Li-ting Yan; Ge Zhang; Min Liu; Lian-ming Zheng (Frontiers in Marine Science, 2021)
Sansha Bay (26.40−27.00°N, 119.50−120.20°E) is a typical semi-enclosed bay, located in northern Fujian Province, China, and adjacent to the East China Sea. The ichthyoplankton species composition and assemblage structure were investigated based on monthly sampling at 25 stations in April−September 2019, covering the important spring and summer spawning seasons in the region. Sampling was conducted in the first 3−5 days of the full moon or new moon phases using a standard plankton net through horizontal and vertical tows during daytime. In total, 25,819 ichthyoplankton samples were collected, of which 25,449 samples (i.e., 24,757 eggs and 692 larvae) were from horizontal tows. For horizontal tow samples, the ichthyoplankton were classified into 58 taxa in 15 orders and 23 families with a combination of external morphology and DNA barcoding analyses, from pelagic to demersal and benthic species. The dominant order was the Gobiiformes, including 23 species (39.7% of all species). The dominant taxa, in terms of relative abundance and frequency of occurrence, consisted of commercially important fishes, such as Setipinna tenuifilis (Valenciennes, 1848) (Engraulidae), Epinephelus akaara (Temminck and Schlegel, 1842) (Serraenidae), Collichthys lucidus (Richardson, 1844), Nibea albiflora (Richardson, 1846) (Sciaenidae), Acanthopagrus schlegelii (Bleeker, 1854), and Pagrus major (Temminck and Schlegel, 1843) (Sparidae), accounting for 78.9% of the horizontal tow samples. Low-valued and small-sized fishes, such as Stolephorus commersonnii Lacepède, 1803 (Engraulidae), Solea ovata Richardson, 1846 (Soleidae), Nuchequula nuchalis (Temminck and Schlegel, 1845), and Photopectoralis bindus (Valenciennes, 1835) (Leiognathidae), were also dominant species, accounting for 11.4% of the horizontal tow samples. The ichthyoplankton assemblage was categorized into five different temporal assemblages based on the cluster and nonmetric multidimensional scaling analysis, namely, April, May, June, July, and August−September (ANOSIM, Global R = 0.656, p < 0.01) with the highest density and richness of ichthyoplankton occurred in May. The spatial distribution pattern showed that the high density (ind./m 3 ) of ichthyoplankton occurred mainly in S12–S25 in Guanjingyang and along the Dongchong Peninsula coastline into Dongwuyang, while low density occurred mainly in S01–S11 in the northwest waters of Sandu Island (ANOVA, F = 8.270, p < 0.05). Temperature, salinity, and chlorophyll a were key factors structuring the ichthyoplankton assemblages in Sansha Bay. In addition, this study revealed the changes of the ichthyoplankton composition, density, and spatial distribution in Sansha Bay over the past three decades.

Deficiency of Klc2 Induces Low-Frequency Sensorineural Hearing Loss in C57BL/6 J Mice and Human - Xiaolong Fu; Yachun An; Hongyang Wang; Peipei Li; Jing Lin; Jia Yuan; Rongyu Yue; Yecheng Jin; Jiangang Gao; Renjie Chai (Molecular Neurobiology, 2021)

Nucleophosmin/B23 promotes endometrial cancer cell escape from macrophage phagocytosis by increasing CD24 expression - Chiao-Yun Lin; Chia-Lung Tsai; Angel Chao; Li-Yu Lee; Wei-Chun Chen; Yun-Hsin Tang; An-Shine Chao; Chyong-Huey Lai (Journal of Molecular Medicine, 2021)

Evaluation of Shale Reservoir Quality by Geophysical Logging for Shuijingtuo Formation of Lower Cambrian in Yichang Area, Central Yangtze - Xiaohong Chen; Lin Chen; Shu Jiang; An Liu; Shengyuan Luo; Hai Li; Peijun Li; Ping Chen (Journal of Earth Science, 2021)

Glaciibacter flavus sp. nov., isolated from a lichen sample - De-Feng An; Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Ming-Guo Jiang; Lei Lang; Li-Song Wang; Johannes F. Imhoff; Cheng-Lin Jiang; Yi Jiang (Archives of Microbiology, 2021)

Removal of Mn(II) by a nitrifying bacterium Acinetobacter sp. AL-6: efficiency and mechanisms - Qiang An; Lin Jin; Shuman Deng; Zheng Li; Chenyi Zhang (Environmental Science and Pollution Research, 2021)

The regional difference in engineering-control and tillage factors of Chinese Soil Loss Equation - Rui-yin Chen; Dong-chun Yan; An-bang Wen; Zhong-lin Shi; Jia-cun Chen; Yuan Liu; Tai-li Chen (Journal of Mountain Science, 2021)

Evaluation and application of an efficient plant DNA extraction protocol for laboratory and field testing - Qi Wang; Xiaoxia Shen; Tian Qiu; Wei Wu; Lin Li; Zhi’an Wang; Huixia Shou (Journal of Zhejiang University-SCIENCE B, 2021)

First report of turnip mosaic virus on yellow passion fruit in China - Li Juan Chen; Xing Xing Zhang; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2021)

Paracoccus lichenicola sp. nov., Isolated from Lichen - Lei Lang; De-Feng An; Long-Qian Jiang; Gui-Ding Li; Li-Song Wang; Xin-Yu Wang; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2021)

Improved control of Frankliniella occidentalis on greenhouse pepper through the integration of Orius sauteri and neonicotinoid insecticides - Qing-cai Lin; Hao Chen; Dirk Babendreier; Jin-ping Zhang; Feng Zhang; Xiao-yan Dai; Zuo-wen Sun; Zhao-peng Shi; Xiao-lin Dong; Guang-an Wu; Yi Yu; Li Zheng; et al. (Journal of Pest Science, 2021)

Multifractal characteristics and spatial variability of soil particle-size distribution in different land use patterns in a small catchment of the Three Gorges Reservoir Region, China - Tai-li Chen; Zhong-lin Shi; An-bang Wen; Dong-chun Yan; Jin Guo; Jia-cun Chen; Yuan Liu; Rui-yin Chen (Journal of Mountain Science, 2021)

First report of ramie mosaic virus on passion fruit in Guangdong, southern China - Li Juan Chen; Dong Lei Sun; Ying Lin Lu; Yu Xing An (Journal of Plant Pathology, 2020)

Effects of intercropping accumulator plants and applying their straw on the growth and cadmium accumulation of Brassica chinensis L. - Yi Tang; Liming Wang; Yongdong Xie; Xuena Yu; LiJin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Guochao Sun; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2020)

Evaluating the severity of building fires with the analytical hierarchy process, big data analysis, and remote sensing - Ching-An Lee; Yu-Chi Sung; Yuan-Shang Lin; Gary Li-Kai Hsiao (Natural Hazards, 2020)

Dietary risk assessment of pesticide residues on Tremella fuciformis Berk (snow fungus) from Fujian Province of China - Qinghua Yao; Sun-an Yan; Hanzhen Chen; Jie Li; Qiu Lin (Food Additives & Contaminants: Part A, 2020)

Alfalfa MsCBL4 enhances calcium metabolism but not sodium transport in transgenic tobacco under salt and saline–alkali stress - Yimin An; Xiao-Xue Yang; Lishuang Zhang; Jun Zhang; Binghao Du; Lin Yao; Xiu-ting Li; Changhong Guo (Plant Cell Reports, 2020)

Nakamurella albus sp. nov.: A Novel Actinobacterium Isolated from a Lichen Sample - Long-Qian Jiang; De-Feng An; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Lei Lang; Ming-Guo Jiang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Reconnaissance and learning after the February 6, 2018, earthquake in Hualien, Taiwan - Jui-Liang Lin; Chun-Hsiang Kuo; Yu-Wen Chang; Shu-Hsien Chao; Yi-An Li; Wen-Cheng Shen; Chung-Han Yu; Cho-Yen Yang; Fan-Ru Lin; Hsiao-Hui Hung; Chun-Chung Chen; Chin-Kuo Su; et al. (Bulletin of Earthquake Engineering, 2020)

Experimental investigation for dynamic instability of coal-rock masses in horizontal section mining of steeply inclined coal seams - Zheng-yi Wang; Lin-ming Dou; Jiang He; An-ye Cao; Xiong-wei Li; Peng-bo Li; Chang-sheng Wu (Arabian Journal of Geosciences, 2020)

Selenium accumulation characteristics of Cyphomandra betacea (Solanum betaceum) seedlings - Linjin Lin; Jing Sun; Tonghao Cui; Xiong Zhou; Ming’an Liao; Yunmin Huan; Liu Yang; Caifang Wu; Xianmin Xia; Yuxi Wang; Zhiyu Li; Jinpeng Zhu; et al. (Physiology and Molecular Biology of Plants, 2020)

Miscanthus cultivation shapes rhizosphere microbial community structure and function as assessed by Illumina MiSeq sequencing combined with PICRUSt and FUNGUIld analyses - Yan Chen; Wei Tian; Yang Shao; Ying-Jun Li; Li-An Lin; Ying-Jun Zhang; Hui Han; Zhao-Jin Chen (Archives of Microbiology, 2020)

Effects of carboxymethyl chitosan on the growth and nutrient uptake in Prunus davidiana seedlings - Dandi Xu; Hongyan Li; Lijin Lin; Ming’an Liao; Qunxian Deng; Jin Wang; Xiulan Lv; Honghong Deng; Dong Liang; Hui Xia (Physiology and Molecular Biology of Plants, 2020)

Morphological characteristics and genetic diversity of Colletotrichum horii infecting persimmon tree in China - Quan-en Deng; Xiang-yang Ding; Jian-an Li; Lin-kai Cui; Jian-qiang Xu (European Journal of Plant Pathology, 2020)

Aureimonas leprariae sp. nov., Isolated from a Lepraria sp. Lichen - Kun Zhang; Long-Qian Jiang; Li-Song Wang; De-Feng An; Lei Lang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2020)

Characterization and fine mapping of qkrnw4, a major QTL controlling kernel row number in maize - Ningning Nie; Xiaoyu Ding; Lin Chen; Xun Wu; Yixin An; Chunhui Li; Yanchun Song; Dengfeng Zhang; Zhizhai Liu; Tianyu Wang; Yu Li; Yong-xiang Li; et al. (Theoretical and Applied Genetics, 2019)

Microfluidic tools for lipid production and modification: a review - Jin-Zheng Wang; Lin-Lin Zhu; Fan Zhang; Richard Ansah Herman; Wen-Jing Li; Xue-Jiao Zhou; Fu-An Wu; Jun Wang (Environmental Science and Pollution Research, 2019)

Experimental study on the physical modeling of loess tunnel-erosion rate - Li Wang; Xi-An Li; Lin-Cui Li; Bo Hong; Jia Liu (Bulletin of Engineering Geology and the Environment, 2019)

Rubellimicrobium rubrum sp. nov., a novel bright reddish bacterium isolated from a lichen sample - Long-Qian Jiang; Kun Zhang; Gui-Ding Li; Xin-Yu Wang; Song-Biao Shi; Qin-Yuan Li; De-Feng An; Lei Lang; Li-Song Wang; Cheng-Lin Jiang; Yi Jiang (Antonie van Leeuwenhoek, 2019)

Effects of mutual grafting on cadmium accumulation characteristics of first post-generations of Bidens pilosa L. and Galinsoga parviflora Cav. - Hongyan Li; Jin Wang; Lijin Lin; Ming’an Liao; Xiulan Lv; Yi Tang; Xun Wang; Hui Xia; Dong Liang; Wei Ren; Wei Jiang (Environmental Science and Pollution Research, 2019)

A Novel Event Detection Model for Water Distribution Systems Based on Data-Driven Estimation and Support Vector Machine Classification - Xiang-Yun Zou; Yi-Li Lin; Bin Xu; Zi-Bo Guo; Sheng-Ji Xia; Tian-Yang Zhang; An-Qi Wang; Nai-Yun Gao (Water Resources Management, 2019)

Effects of self-rooted grafting on growth and cadmium accumulation in post-grafting generations of soybean (Glycine max) - Jin Wang; Huan Yao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Xiulan Lv; Ming’an Liao; Guochao Sun; Huanxiu Li; Xun Wang; Wei Ren (Environmental Monitoring and Assessment, 2019)

Experimental study on the disintegration of loess in the Loess Plateau of China - Xi-An Li; Li Wang; Yong-li Yan; Bo Hong; Lin-Cui Li (Bulletin of Engineering Geology and the Environment, 2019)

Using two contrasting methods with the same tracers to trace the main sediment source in a mountainous catchment - Han Wu; Dong-hong Xiong; Su Zhang; Yong Yuan; Wan-Xin Li; Lin Liu; Zheng-an Su; Xiao-ning Lu (Journal of Mountain Science, 2019)

Cloud Radiative Feedbacks during the ENSO Cycle Simulated by CAMS-CSM - Lin Chen; Lijuan Hua; Xinyao Rong; Jian Li; Lu Wang; Guo Zhang; Ming Sun; Zi’an Ge (Journal of Meteorological Research, 2019)

Loss of soil microbial diversity exacerbates spread of antibiotic resistance - Qing-Lin Chen; Xin-Li An; Bang-Xiao Zheng; Michael Gillings; Josep Peñuelas; Li Cui; Jian-Qiang Su; Yong-Guan Zhu (Soil Ecology Letters, 2019)

3D stability of partially saturated soil slopes after rapid drawdown by a new layer-wise summation method - Long Wang; De’an Sun; Lin Li (Landslides, 2019)

Cadmium-accumulator straw application alleviates cadmium stress of lettuce (Lactuca sativa) by promoting photosynthetic activity and antioxidative enzyme activities - Yi Tang; Yongdong Xie; Guochao Sun; Huaqiang Tan; Lijin Lin; Huanxiu Li; Ming’an Liao; Zhihui Wang; Xiulan Lv; Dong Liang; Hui Xia; Xun Wang; et al. (Environmental Science and Pollution Research, 2018)

Elatostema brachyodontum subsp. lengshuiheensis (Urticaceae), a new subspecies from Guizhou, China - Yun Lin; Ming-Tai An; Zhi-Rong Yang; Yan-Qiang Dai; Deng-Li Yu (Kew Bulletin, 2018)

Effects of dietary supplementation with algal astaxanthin on growth, pigmentation, and antioxidant capacity of the blood parrot ( Cichlasoma citrinellum × Cichlasoma synspilum ) - Feng Li; Shuiying Huang; Xiaoxia Lu; Jun Wang; Mingwei Lin; Yu An; Shaoting Wu; Minggang Cai (Journal of Oceanology and Limnology, 2018)

The regulation of skeletal muscle fiber-type composition by betaine is associated with NFATc1/MyoD - Jingjing Du; Linyuan Shen; Peiwen Zhang; Zhendong Tan; Xiao Cheng; Jia Luo; Xue Zhao; Qiong Yang; Hao Gu; An’an Jiang; Jideng Ma; Qianzi Tang; et al. (Journal of Molecular Medicine, 2018)

24-Epibrassinolide-induced alterations in the root cell walls of Cucumis sativus L. under Ca(NO3)2 stress - Ya-Hong An; Heng Zhou; Ying-Hui Yuan; Lin Li; Jin Sun; Sheng Shu; Shi-Rong Guo (Protoplasma, 2018)

Overexpression of Nogo receptor 3 (NgR3) correlates with poor prognosis and contributes to the migration of epithelial cells of nasopharyngeal carcinoma patients - Jiang-Yi He; Ping Han; Yu Zhang; Yong-Dong Liu; Shi-Jian Song; Guo-Kai Feng; Yu An; Ai-Jun Zhou; Hong-Bo Wang; Li Yuan; Zhi-Rui Lin; Tian-Liang Xia; et al. (Journal of Molecular Medicine, 2018)

Effects of indole-3-butytric acid on lead and zinc accumulations in Pseudostellaria maximowicziana - Zhi Ran; Cheng Chen; Fabo Chen; Ming’an Liao; Lijin Lin; Xiulan Lv; Qunxian Deng; Xun Wang; Jin Wang; Yi Tang; Huaxiong Li (Environmental Monitoring and Assessment, 2018)

Effects of melatonin on the growth and cadmium characteristics of Cyphomandra betacea seedlings - Lijin Lin; Jianhua Li; Fabo Chen; Ming’an Liao; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2018)

Evidence that NF-κB and MAPK Signaling Promotes NLRP Inflammasome Activation in Neurons Following Ischemic Stroke - David Yang-Wei Fann; Yun-An Lim; Yi-Lin Cheng; Ker-Zhing Lok; Prasad Chunduri; Sang-Ha Baik; Grant R. Drummond; S. Thameem Dheen; Christopher G. Sobey; Dong-Gyu Jo; Christopher Li-Hsian Chen; Thiruma V. Arumugam (Molecular Neurobiology, 2018)

Climatology of cloud-base height from long-term radiosonde measurements in China - Yong Zhang; Lejian Zhang; Jianping Guo; Jinming Feng; Lijuan Cao; Yang Wang; Qing Zhou; Liangxu Li; Bai Li; Hui Xu; Lin Liu; Ning An; et al. (Advances in Atmospheric Sciences, 2018)

Effects of mutual intercropping on the cadmium accumulation in accumulator plants Stellaria media, Malachium aquaticum, and Galium aparine - Qiyu Lu; Jianhua Li; Fabo Chen; Ming’an Liao; Lijin Lin; Yi Tang; Dong Liang; Hui Xia; Yunsong Lai; Xun Wang; Cheng Chen; Wei Ren (Environmental Monitoring and Assessment, 2017)

Numerical investigation of the evolution of overlying strata and distribution of static and dynamic loads in a deep island coal panel - Guang-an Zhu; Lin-ming Dou; Chang-bin Wang; Jing Li; Wu Cai; Zi-wei Ding (Arabian Journal of Geosciences, 2017)

Hyperaccumulator straw improves the cadmium phytoextraction efficiency of emergent plant Nasturtium officinale - Keqiang Li; Lijin Lin; Jin Wang; Hui Xia; Dong Liang; Xun Wang; Ming’an Liao; Li Wang; Li Liu; Cheng Chen; Yi Tang (Environmental Monitoring and Assessment, 2017)

Case Study of Passive Seismic Velocity Tomography in Rock Burst Hazard Assessment During Underground Coal Entry Excavation - Guang-an Zhu; Lin-ming Dou; Wu Cai; Zhen-lei Li; Min Zhang; Yong Kong; Wei Shen (Rock Mechanics and Rock Engineering, 2016)

Mining-induced stress changes and rock burst control in a variable-thickness coal seam - Guang-an Zhu; Lin-ming Dou; Zhen-lei Li; Wu Cai; Yong Kong; Jing Li (Arabian Journal of Geosciences, 2016)

The effects of abscisic acid (ABA) addition on cadmium accumulation of two ecotypes of Solanum photeinocarpum - Jin Wang; Lijin Lin; Li Luo; Ming’an Liao; Xiulan Lv; Zhihui Wang; Dong Liang; Hui Xia; Xun Wang; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Parenting stress and affective symptoms in parents of autistic children - Yun Gong; YaSong Du; HuiLin Li; XiYan Zhang; Yu An; Bai-Lin Wu (Science China Life Sciences, 2015)

Protective Effect of Apigenin on Ischemia/Reperfusion Injury of the Isolated Rat Heart - Jing Hu; Zilin Li; Li-ting Xu; Ai-jun Sun; Xiao-yan Fu; Li Zhang; Lin-lin Jing; An-dong Lu; Yi-fei Dong; Zheng-ping Jia (Cardiovascular Toxicology, 2015)

P2X7 receptor of rat dorsal root ganglia is involved in the effect of moxibustion on visceral hyperalgesia - Shuangmei Liu; Qingming Shi; Qicheng Zhu; Ting Zou; Guilin Li; An Huang; Bing Wu; Lichao Peng; Miaomiao Song; Qin Wu; Qiuyu Xie; Weijian Lin; et al. (Purinergic Signalling, 2015)

Dorsal hippocampal brain receptor complexes linked to the protein synthesis-dependent late phase (LTP) in the rat - Lin Li; Han Wang; Maryam Ghafari; Gunyong An; Volker Korz; Gert Lubec (Brain Structure and Function, 2015)

Oricola cellulosilytica gen. nov., sp. nov., a cellulose-degrading bacterium of the family Phyllobacteriaceae isolated from surface seashore water, and emended descriptions of Mesorhizobium loti and Phyllobacterium myrsinacearum - Asif Hameed; Mariyam Shahina; Wei-An Lai; Shih-Yao Lin; Li-Sen Young; You-Cheng Liu; Yi-Han Hsu; Chiu-Chung Young (Antonie van Leeuwenhoek, 2015)

Resource availability differentially drives community assemblages of plants and their root-associated arbuscular mycorrhizal fungi - Yongjun Liu; Lin Mao; Junyong Li; Guoxi Shi; Shengjing Jiang; Xiaojun Ma; Lizhe An; Guozhen Du; Huyuan Feng (Plant and Soil, 2015)

Youngia erythrocarpa, a newly discovered cadmium hyperaccumulator plant - Lijin Lin; Bo Ning; Ming’an Liao; Yajun Ren; Zhihui Wang; Yingjie Liu; Ji Cheng; Li Luo (Environmental Monitoring and Assessment, 2015)

Spatial distribution characteristics of surface tidal currents in the southwest of Taiwan Strait - Zhiben Shen; Xiongbin Wu; Hang Lin; Xiaofeng Chen; Xing’an Xu; Lun Li (Journal of Ocean University of China, 2014)

Impacts of uncertainty in AVOC emissions on the summer ROx budget and ozone production rate in the three most rapidly-developing economic growth regions of China - Feng Wang; Junling An; Ying Li; Yujia Tang; Jian Lin; Yu Qu; Yong Chen; Bing Zhang; Jing Zhai (Advances in Atmospheric Sciences, 2014)

Endophytic nitrogen-fixing Klebsiella variicola strain DX120E promotes sugarcane growth - Chun-Yan Wei; Li Lin; Li-Jing Luo; Yong-Xiu Xing; Chun-Jin Hu; Li-Tao Yang; Yang-Rui Li; Qianli An (Biology and Fertility of Soils, 2014)

Heterologous expression of artificial miRNAs from rice dwarf virus in transgenic rice - Runhong Sun; Peng Du; Lin Jiang; Derong An; Yi Li (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

The relationship between typhoons' peripheral circulation and ground-level ozone concentrations in central Taiwan - Wan-Li Cheng; Li-Wei Lai; Walter Den; Meng-Ting Wu; Chao-An Hsueh; Pay-Liam Lin; Chueh-Ling Pai; Yeou-Lih Yan (Environmental Monitoring and Assessment, 2014)

Wheat cultivars form distinctive communities of root-associated arbuscular mycorrhiza in a conventional agroecosystem - Lin Mao; Yongjun Liu; Guoxi Shi; Shengjing Jiang; Gang Cheng; Xingmao Li; Lizhe An; Huyuan Feng (Plant and Soil, 2014)

Partial least squares based identification of Duchenne muscular dystrophy specific genes - Hui-bo An; Hua-cheng Zheng; Li Zhang; Lin Ma; Zheng-yan Liu (Journal of Zhejiang University-SCIENCE B, 2013)

Functional identification of the gene encoding the enzyme involved in mannosylation in ramoplanin biosynthesis in Actinoplanes sp. - Jun-Sheng Chen; Yuan-Xi Wang; Lei Shao; Hai-Xue Pan; Ji-An Li; Hui-Min Lin; Xiao-Jing Dong; Dai-Jie Chen (Biotechnology Letters, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

β2-Glycoprotein I inhibits VEGF-induced endothelial cell growth and migration via suppressing phosphorylation of VEGFR2, ERK1/2, and Akt - Wen-Chin Chiu; Jan-Yu Lin; Tzong-Shyuan Lee; Li-Ru You; An-Na Chiang (Molecular and Cellular Biochemistry, 2013)

Development of a substrate-coupled biocatalytic process driven by an NADPH-dependent sorbose reductase from Candida albicans for the asymmetric reduction of ethyl 4-chloro-3-oxobutanoate - Ping Cai; Mingdong An; Lin Xu; Sheng Xu; Ning Hao; Yan Li; Kai Guo; Ming Yan (Biotechnology Letters, 2012)

Photocatalytic Degradation of Reactive Black 5 by Fish Scale-Loaded TiO2 Composites - Li-Ngee Ho; Soon-An Ong; Yee Lin See (Water, Air, & Soil Pollution, 2012)

Overexpression of microRNA-378 attenuates ischemia-induced apoptosis by inhibiting caspase-3 expression in cardiac myocytes - Ji Fang; Xiao-Wei Song; Jing Tian; Hu-Yan Chen; Dong-Feng Li; Jian-Fei Wang; An-Jing Ren; Wen-Jun Yuan; Li Lin (Apoptosis, 2012)

Functional analysis of Waardenburg syndrome-associated PAX3 and SOX10 mutations: report of a dominant-negative SOX10 mutation in Waardenburg syndrome type II - Hua Zhang; Hongsheng Chen; Hunjin Luo; Jing An; Lin Sun; Lingyun Mei; Chufeng He; Lu Jiang; Wen Jiang; Kun Xia; Jia-Da Li; Yong Feng (Human Genetics, 2012)

Association of SERPINE2 gene with the risk of chronic obstructive pulmonary disease and spirometric phenotypes in northern Han Chinese population - Li An; Ting Yang; Yongbiao Zhang; Yingxiang Lin; Hong Zhang; Xia Jiao; Lin Hua; Huaping Dai; Chen Wang (Molecular Biology Reports, 2012)

QTL detection of seven quality traits in wheat using two related recombinant inbred line populations - Jun Li; Fa Cui; An-ming Ding; Chun-hua Zhao; Xiu-qin Wang; Lin Wang; Yin-guang Bao; Xiao-lei Qi; Xing-feng Li; Ju-rong Gao; De-shun Feng; Hong-gang Wang (Euphytica, 2012)

Construction and characterization of a normalized cDNA library from the river snail Bellamya aeruginosa after exposure to copper - Zi-Cheng Li; Li-Hui An; Qing Fu; Ying Liu; Lei Zhang; Hao Chen; Xing-Ru Zhao; Li-Jing Wang; Bing-Hui Zheng; Lin-Bo Zhang (Ecotoxicology, 2012)

Effect of Low-Intensity Pulsed Ultrasound on MMP-13 and MAPKs Signaling Pathway in Rabbit Knee Osteoarthritis - Xueping Li; Jianan Li; Kai Cheng; Qiang Lin; Daxin Wang; Hongfei Zhang; Hengyuan An; Mingxia Gao; Anliang Chen (Cell Biochemistry and Biophysics, 2011)

Precise mapping Fhb5, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Feng Xu; Mingzhi Tang; Yan Zhou; Guoqiang Li; Xia An; Feng Lin; Haibin Xu; Haiyan Jia; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2011)

Ningdong granule: a complementary and alternative therapy in the treatment of attention deficit/hyperactivity disorder - Ji-Jun Li; Zai-Wang Li; Shu-Zhen Wang; Fang-Hua Qi; Lin Zhao; Hong Lv; An-Yuan Li (Psychopharmacology, 2011)

Levels and Congener Profiles of Particle-bound Polybrominated Dibenzo-p-dioxins/furans (PBDD/Fs) in Ambient Air around Guangzhou, China - Huiru Li; Lin Zhou; Ligui Mo; Ping’an Peng; Guoying Sheng; Jiamo Fu; Zhiqiang Yu (Bulletin of Environmental Contamination and Toxicology, 2011)

Regulation of expression of trehalose-6-phosphate synthase during cold shock in Arthrobacter strain A3 - Xi-Ming Chen; Ying Jiang; Yuan-Ting Li; Hai-Hong Zhang; Jie Li; Xing Chen; Qi Zhao; Jing Zhao; Jing Si; Zhi-Wei Lin; Hua Zhang; Paul Dyson; et al. (Extremophiles, 2011)

Novel Fluorescent Molecular Clips: Selective Recognition Towards Fe3+ in Aqueous Solution - Lin Li; Neng-fang She; Zhuan Fei; Pui-kin So; Yu-zhou Wang; Li-ping Cao; An-xin Wu; Zhong-ping Yao (Journal of Fluorescence, 2011)

Analysis of the Composition and Characteristics of Culturable Endophytic Bacteria Within Subnival Plants of the Tianshan Mountains, Northwestern China - Hong Mei Sheng; Hong Shan Gao; Lin Gui Xue; Shuo Ding; Chun Li Song; Hu Yuan Feng; Li Zhe An (Current Microbiology, 2011)

Isolation of a LEAFY homolog from Populus tomentosa: expression of PtLFY in P. tomentosa floral buds and PtLFY-IR-mediated gene silencing in tobacco (Nicotiana tabacum) - Xin-Min An; Dong-Mei Wang; Ze-Liang Wang; Bo Li; Wen-Hao Bo; Guan-Lin Cao; Zhi-Yi Zhang (Plant Cell Reports, 2011)

Relation of uric acid levels to aortic root dilatation in hypertensive patients with and without metabolic syndrome - Li-jiang Tang; Jian-jun Jiang; Xiao-feng Chen; Jian-an Wang; Xian-fang Lin; Yu-xi Du; Cong-feng Fang; Zhao-xia Pu (Journal of Zhejiang University-SCIENCE B, 2010)

Fine mapping Fhb4, a major QTL conditioning resistance to Fusarium infection in bread wheat (Triticum aestivum L.) - Shulin Xue; Guoqiang Li; Haiyan Jia; Feng Xu; Feng Lin; Mingzhi Tang; Yao Wang; Xia An; Haibin Xu; Lixia Zhang; Zhongxin Kong; Zhengqiang Ma (Theoretical and Applied Genetics, 2010)

Proteomic Analysis of Interactions Between the Generalist Herbivore Spodoptera exigua (Lepidoptera: Noctuidae) and Arabidopsis thaliana - Ju-Hong Zhang; Li-Wen Sun; Lin-Lin Liu; Jie Lian; Shao-Li An; Xu Wang; Jing Zhang; Jun-Ling Jin; Shan-Yu Li; Jing-Hui Xi (Plant Molecular Biology Reporter, 2010)

Numerical Simulations on the Effect of Sea–Land Breezes on Atmospheric Haze over the Pearl River Delta Region - Chen Xun-lai; Feng Ye-rong; Li Jiang-nan; Lin Wen-shi; Fan Shao-jia; Wang An-yu; Fong Soikun; Lin Hui (Environmental Modeling & Assessment, 2009)

A cell strain cloned from Spodoptera exigua cell line (IOZCAS-Spex-II) highly susceptible to S. exigua nucleopolyhedrovirus infection - Huan Zhang; Yong-an Zhang; Qilian Qin; Xuan Li; Lin Miao; Yuzhu Wang; Liangjian Qu; Aijun Zhang; Qing Yang (In Vitro Cellular & Developmental Biology - Animal, 2009)

Shear-wave splitting in the southeast of Cathaysia block, South China - Yuan Gao; Jing Wu; Jin-An Cai; Yu-Tao Shi; Shu Lin; Ting Bao; Zu-Ning Li (Journal of Seismology, 2009)

5-Hydroxymethyl-2-furfural, a clinical trials agent for sickle cell anemia, and its mono/di-glucosides from classically processed steamed Rehmanniae Radix - An-Shen Lin; Keduo Qian; Yoshihide Usami; Li Lin; Hideji Itokawa; Charleson Hsu; Susan L. Morris-Natschke; Kuo-Hsiung Lee (Journal of Natural Medicines, 2008)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Genotyping of Trichophyton rubrum by analysis of ribosomal-DNA intergenic spacer regions - Guoling Yang; Lijia An; Qiao Li; Jingrong Lin; Weida Liu; Liji Jin; Xiran Lin (Mycopathologia, 2007)

Cloning and characterization of a novel albinism-related zinc finger protein gene in Japanese flounder - Jiaqing Wang; Lin Hou; Xiangyang Zou; Feng Yao; Xiaoyan Li; Xintao Zhao; Ruifeng Zhang; Lijuan Jiang; Wenjing Sun; Jialu An (Fish Physiology and Biochemistry, 2007)

Cloning and identification of partial DNA fragment for the B mating-type factor in Lentinula edodes using degenerate PCR - An-Zheng Li; Xue-Feng Xu; Fan-Xue Lin; Shui-Ming Cheng; Fang-Can Lin (World Journal of Microbiology and Biotechnology, 2007)

Summer rain pulse size and rainwater uptake by three dominant desert plants in a desertified grassland ecosystem in northwestern China - Xiaoli Cheng; Shuqing An; Bo Li; Jiquan Chen; Guanghui Lin; Yuhong Liu; Yiqi Luo; Shirong Liu (Plant Ecology, 2006)

Characterization of Usher syndrome type I gene mutations in an Usher syndrome patient population - Xiao Mei Ouyang; Denise Yan; Li Lin Du; J. Fielding. Hejtmancik; Samuel G. Jacobson; Walter E. Nance; An Ren Li; Simon Angeli; Muriel Kaiser; Valerie Newton; Steve D. M. Brown; Thomas Balkany; et al. (Human Genetics, 2005)

Risk of hepatocellular carcinoma and habits of alcohol drinking, betel quid chewing and cigarette smoking: a cohort of 2416 HBsAg-seropositive and 9421 HBsAg-seronegative male residents in Taiwan - Li-Yu Wang; San-Lin You; Sheng-Nan Lu; Hsi-Chang Ho; Mei-Hui Wu; Chien-An Sun; Hwai-I Yang; Chien-Jen Chen (Cancer Causes & Control, 2003)

Litter decomposition and nitrogen mineralization of soils in subtropical plantation forests of southern China, with special attention to comparisons between legumes and non-legumes - Zhi-an Li; Shao-lin Peng; Debbie J. Rae; Guo-yi Zhou (Plant and Soil, 2001)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)